Secondary battery, electronic apparatus, and vehicle

JP2025025701APending Publication Date: 2025-02-21SEMICON ENERGY LAB CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023130749
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

Smart Images

  • Figure 2025025701000001_ABST
    Figure 2025025701000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode active material of which an internal stress is released, and provide a secondary battery with a high charging and discharging characteristic.SOLUTION: A secondary battery has a positive electrode. The positive electrode includes a positive electrode active material, and the positive electrode active material includes lithium, cobalt, oxygen, and magnesium. The positive electrode active material includes a cluster of magnesium oxide having a rock salt type crystalline structure inside thereof. A circumference of the cluster preferably has nickel. The cluster includes a function of releasing a stress of the positive electrode active material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One embodiment of the present invention relates to an object, a method, or a manufacturing method. Alternatively, the present invention relates to a process, a machine, a manufacture, or a composition of matter. One embodiment of the present invention relates to a power storage device including a secondary battery, a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device, or a manufacturing method thereof.

[0002] In this specification, the term "electronic device" refers to any device having a power storage device, and an electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all classified as electronic devices. [Background technology]

[0003] In recent years, various types of power storage devices have been actively developed, such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries, all-solid-state batteries, etc. In particular, the demand for high-output, high-capacity lithium-ion secondary batteries has rapidly expanded in line with the development of the semiconductor industry, and they have become indispensable in the modern information society as a rechargeable energy source.

[0004] In particular, there is a high demand for secondary batteries with large discharge capacity per weight and excellent cycle characteristics for mobile electronic devices. In order to meet this demand, the improvement of the positive electrode active material of the positive electrode of secondary batteries has been actively carried out (for example, Patent Document 1 and Patent Document 2). In addition, research on the crystal structure of the positive electrode active material has also been carried out (Non-Patent Documents 1 to 3).

[0005] X-ray diffraction (XRD) is one of the techniques used to analyze the crystal structure of positive electrode active materials. XRD data can be analyzed by using the Inorganic Crystal Structure Database (ICSD) introduced in Non-Patent Document 4. For example, the lattice constant of lithium cobalt oxide described in Non-Patent Document 5 can be referenced from ICSD. For Rietveld analysis, for example, the analysis program RIETAN-FP (Non-Patent Document 6) can be used. VESTA (Non-Patent Document 7) can be used as software for drawing crystal structures.

[0006] Also, as image processing software, for example, ImageJ (Non-Patent Documents 8 to 10) is known. By using this software, for example, the shape of the positive electrode active material can be analyzed.

[0007] Microelectron diffraction is also effective for identifying the crystal structure of the positive electrode active material, particularly the crystal structure of the surface layer. For example, the analysis program ReciPro (Non-Patent Document 11) can be used to analyze the electron diffraction pattern. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2018-206747 A [Patent Document 2] Patent Publication No. 2022-070247 [Non-patent literature]

[0009] [Non-Patent Document 1] Toyoki Okumura et.al., “Correlation of lithium ion distribution and X-ray absorption near-edge structure in O3-and O2-lithium cobalt oxides from first-principle calculation”, Journal of Materials Chemistry, 2012, 22, p.17340-17348 [Non-Patent Document 2] Motohashi, T. et.al., “Electronic phase diagram of the layered cobalt oxide system LixCoO2(0.0≦x≦1.0)”, Physical Review B, 80(16);165114 [Non-Patent Document 3] Zhaohui Chen et.al., “Staging Phase Transitions in LixCoO2”, Journal of The Electrochemical Society, 2002, 149(12)A1604-A1609 [Non-Patent Document 4] Belsky, A. et.al., “New developments in the Inorganic Crystal Structure Database (ICSD): accessibility in support of materials research and design”, Acta Cryst., (2002) B58 364-369. [Non-Patent Document 5] Akimoto, J.; Gotoh, Y.; Oosawa, Y. “Synthesis and structural refinement of LiCoO2 single crystals” Journal of Solid State Chemistry (1998) 141, p. 298-302. [Non-Patent Document 6] F.Izumi and K.Momma,,“Three-Dimensional Visualization in Powder Diffraction” Solid State Phenom.130,15-20(2007);

Direct Environment 7

Outdoor Tools 8

Outdoor Tools9

Outdoor Tools 10

Outdoor Content11

[0010] There is still room for improvement in various aspects of lithium-ion secondary batteries, such as discharge capacity, cycle characteristics, reliability, safety, and cost. For example, it is known that lithium cobalt oxide expands and contracts in the c-axis direction during charging and discharging. If the internal stress generated at this time could be alleviated, the collapse of the crystal structure caused by repeated charging and discharging could be suppressed, and it is expected that the charge-discharge cycle characteristics would be improved.

[0011] In view of the above, an object of one embodiment of the present invention is to provide a positive electrode active material or composite oxide that can be used in a lithium ion secondary battery and in which internal stress is alleviated.Another object is to provide a positive electrode active material or composite oxide in which a decrease in discharge capacity during charge and discharge cycles is suppressed.Another object is to provide a positive electrode active material or composite oxide whose crystal structure is not easily deformed even after repeated charge and discharge.Another object is to provide a positive electrode active material or composite oxide with a large discharge capacity.Another object is to provide a secondary battery or vehicle with high safety or reliability.

[0012] Another object of one embodiment of the present invention is to provide a positive electrode active material, a composite oxide, a power storage device, or a manufacturing method thereof.

[0013] Note that the description of these problems does not preclude the existence of other problems. Note that one embodiment of the present invention does not necessarily solve all of these problems. Note that it is possible to extract problems other than these from the description of the specification, drawings, and claims. [Means for solving the problem]

[0014] In order to solve the above problems, in one embodiment of the present invention, regions having a stress relaxation function are dispersed inside a positive electrode active material.

[0015] One embodiment of the present invention is a secondary battery having a positive electrode. The positive electrode has a positive electrode active material. The positive electrode active material contains lithium, cobalt, oxygen, and magnesium. The positive electrode active material contains magnesium oxide clusters having a rock salt crystal structure therein.

[0016] Another embodiment of the present invention is a secondary battery having a positive electrode, the positive electrode having a positive electrode active material, the positive electrode active material having lithium, cobalt, oxygen, magnesium and nickel, the positive electrode active material having clusters of magnesium oxide having a rock salt type crystal structure therein, and nickel around the magnesium oxide clusters.

[0017] In the above, it is preferable that the Mg / Ni (atomic ratio) inside the positive electrode active material is 0.8 or more and 1.2 or less.

[0018] In the above, it is preferable that the magnesium oxide clusters have a function of relieving stress of the positive electrode active material.

[0019] Another embodiment of the present invention is an electronic device including any of the above secondary batteries.

[0020] Another embodiment of the present invention is a vehicle including the above-described secondary battery. Effect of the Invention

[0021] According to one embodiment of the present invention, a positive electrode active material or composite oxide that can be used in a lithium ion secondary battery and has a reduced internal stress can be provided. Alternatively, a positive electrode active material or composite oxide in which a decrease in discharge capacity during charge / discharge cycles is suppressed can be provided. Alternatively, a positive electrode active material or composite oxide in which a crystal structure is not easily deformed even after repeated charge / discharge can be provided. Alternatively, a positive electrode active material or composite oxide with a large discharge capacity can be provided. Alternatively, a secondary battery or vehicle with high safety or reliability can be provided.

[0022] According to one embodiment of the present invention, a positive electrode active material, a composite oxide, a power storage device, or a manufacturing method thereof can be provided.

[0023] Note that the description of these effects does not preclude the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of these effects. Note that effects other than these will become apparent from the description in the specification, drawings, claims, etc., and it is possible to extract effects other than these from the description in the specification, drawings, claims, etc. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a schematic diagram illustrating the internal crystal structure of the positive electrode active material. [Diagram 2] FIG. 2 is a schematic diagram illustrating the internal crystal structure of the positive electrode active material. [Diagram 3] FIG. 3 is a cross-sectional view of the positive electrode active material. [Figure 4] 4(A) and 4(B) are diagrams illustrating the results of the DSC analysis. [Diagram 5] Figure 5 is an example of a TEM image in which the crystal orientations are roughly consistent. [Figure 6] Figure 6(A) is an example of a STEM image in which the crystal orientations are roughly consistent, Figure 6(B) is an FFT pattern of the region of the rock-salt-type crystal RS, and Figure 6(C) is an FFT pattern of the region of the layered rock-salt-type crystal LRS. [Figure 7]FIG. 7 is a diagram illustrating the crystal structure of the positive electrode active material. [Figure 8] FIG. 8 is a diagram illustrating the crystal structure of a conventional positive electrode active material. [Figure 9] FIG. 9 shows an XRD pattern calculated from the crystal structure. [Figure 10] FIG. 10 shows an XRD pattern calculated from the crystal structure. [Figure 11] 11(A) and 11(B) show XRD patterns calculated from the crystal structure. [Figure 12] FIG. 12 is a cross-sectional view of the positive electrode active material. [Figure 13] 13A to 13C are diagrams illustrating a method for manufacturing a positive electrode active material. [Figure 14] FIG. 14 is a diagram illustrating a method for producing a positive electrode active material. [Figure 15] 15A to 15C are diagrams illustrating a method for manufacturing a positive electrode active material. [Figure 16] FIG. 16 is a diagram showing the external appearance of a secondary battery. [Figure 17] 17A to 17C are diagrams illustrating a method for manufacturing a secondary battery. [Figure 18] 18A to 18H are diagrams illustrating examples of electronic devices. [Figure 19] 19A to 19D are diagrams illustrating examples of electronic devices. [Figure 20] 20A to 20C are diagrams illustrating examples of electronic devices. [Figure 21] 21(A) to 21(C) are diagrams illustrating an example of a vehicle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In the following, examples of embodiments of the present invention will be described with reference to the drawings, etc. However, the present invention should not be interpreted as being limited to the following examples. The embodiments of the present invention can be modified without departing from the spirit of the present invention.

[0026] In this specification, the space group is expressed using the short notation of the international notation (or Hermann-Mauguin notation). The crystal plane and crystal direction are expressed using Miller indices. In crystallography, the space group, crystal plane, and crystal direction are expressed by adding a superscript bar to the number, but in this specification, due to format restrictions, instead of adding a bar above the number, a - (minus sign) may be added before the number. In addition, individual directions indicating directions within a crystal are expressed with [ ], collective directions indicating all equivalent directions are expressed with < >, individual planes indicating crystal planes are expressed with ( ), and collective planes with equivalent symmetry are expressed with {}. In addition, trigonal crystals expressed by the space group R-3m are generally sometimes expressed as a composite hexagonal lattice of hexagonal crystals for ease of understanding the structure. In addition, not only (hkl) but also (hkil) may be used as Miller indices. Here, i is -(h+k). In this specification, the crystal planes of the space group R-3m are expressed as a composite hexagonal lattice unless otherwise specified.

[0027] In this specification, when simply referring to a positive electrode active material, there are cases where a description is given of a plurality of positive electrode active material particles and cases where a description is given of a single positive electrode active material particle, depending on the analytical method, etc. For example, in the case of descriptions regarding scanning transmission electron microscope-energy dispersive X-ray fluorescence detector (STEM-EDX) line analysis, STEM-electron energy loss spectroscopy (STEM-EELS), and electron diffraction, the description is given of a single positive electrode active material particle unless otherwise specified. On the other hand, in the case of X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), various mass analyses, etc., the description is given of a plurality of positive electrode active material particles unless otherwise specified.

[0028] In this specification and the like, the particle is not limited to a spherical shape (a circular cross-sectional shape), but may be an ellipse, a rectangle, a trapezoid, a triangle, a square with rounded corners, an asymmetrical shape, or the like in cross section, and each particle may be an irregular shape. In addition, when simply referring to a particle, it includes primary particles and secondary particles.

[0029] When describing the characteristics of the particles of the positive electrode active material, it is not necessarily required that all particles have such characteristics. For example, if 50% or more, preferably 70% or more, more preferably 90% or more of randomly selected three or more particles of the positive electrode active material have the preferable characteristics described below, it can be said that there is a sufficient effect of improving the characteristics of the positive electrode active material and the secondary battery having the same.

[0030] The distribution of a certain element shall refer to a region where the element is continuously detected within a range that is not noise by a certain continuous analysis method. The region where the element is continuously detected within a range that is not noise can also be, for example, a region that is always detected when the analysis is performed multiple times.

[0031] The theoretical capacity of the positive electrode active material refers to the amount of electricity when all the insertable and removable lithium in the positive electrode active material has been removed. For example, the theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 275 mAh / g, and the theoretical capacity of LiMn2O4 is 148 mAh / g.

[0032] Also, the amount of remaining insertable and removable lithium in the positive electrode active material is represented by x in the composition formula, for example, x in Li x MO2 (where M is one or more selected from cobalt, nickel, and manganese). In the case of the positive electrode active material in the secondary battery, x = (theoretical capacity - charged capacity) / theoretical capacity can be used. For example, when a secondary battery using LiMO2 as the positive electrode active material is charged to 219.2 mAh / g, it can be said that Li 0.2 MO2 or x = 0.2. When x in Li x MO2 is small, it means, for example, 0.1 < x ≤ 0.24. In some cases, the amount of lithium desorbed from the positive electrode active material relative to the theoretical capacity is indicated as the depth of charge. In this specification and the like, the depth of charge = 1 - x.

[0033] For example, when properly synthesized lithium cobalt oxide before use in the positive electrode approximately satisfies the stoichiometric ratio, it is LiCoO2 and x = 1. The lithium cobalt oxide contained in a secondary battery that has finished discharging can also be said to be LiCoO2 and x = 1. The end of discharge here refers to a state in which the voltage is 3.0V or 2.5V or less at a current of 100mA / g or less.

[0034] Li x It is preferable that the charge capacity and / or discharge capacity used in calculating x in MO2 be measured under conditions that are free of or have little influence from short circuits and / or decomposition of the electrolyte, etc. For example, data from a secondary battery that has experienced a sudden change in capacity that is considered to be due to a short circuit should not be used in calculating x.

[0035] The space group of a crystal structure is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification and the like, "belonging to a certain space group," "belonging to a certain space group," or "being a certain space group" can be rephrased as "identified with a certain space group."

[0036] Also, if the arrangement of anions is roughly close to cubic close-packed, it can be considered as cubic close-packed. The arrangement of anions in cubic close-packed refers to a state in which the second layer of anions is arranged above the gaps of the anions packed in the first layer, and the third layer of anions is arranged directly above the gaps of the second layer of anions, but not directly above the anions in the first layer. Therefore, the anions do not have to be strictly cubic lattices. Also, since real crystals always have defects, the analysis results do not necessarily have to be as theoretically correct. For example, in the FFT (fast Fourier transform) pattern of an electron diffraction pattern or a TEM image, etc., spots may appear at positions slightly different from the theoretical positions. For example, if the orientation with respect to the theoretical positions is 5 degrees or less, or 2.5 degrees or less, it can be said to have a cubic close-packed structure.

[0037] A positive electrode active material to which an additive element that improves electrical conductivity and / or an additive element that stabilizes a crystal structure is added may be expressed as a composite oxide, a positive electrode material, a positive electrode material, a positive electrode material for secondary batteries, and the like. In this specification and the like, the positive electrode active material of one embodiment of the present invention preferably has a compound. In this specification and the like, the positive electrode active material of one embodiment of the present invention preferably has a composition. In this specification and the like, the positive electrode active material of one embodiment of the present invention preferably has a composite.

[0038] As the charging voltage of a secondary battery increases, the voltage of the positive electrode generally increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at high voltages. Since the crystal structure of the positive electrode active material is stable in a charged state, it is possible to suppress a decrease in charge / discharge capacity due to repeated charging and discharging.

[0039] Unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) of the secondary battery are described in the state before degradation. The decrease in discharge capacity due to aging and burn-in treatments during the secondary battery manufacturing stage is not called degradation. For example, when a lithium-ion secondary cell and a lithium-ion secondary battery pack (hereinafter referred to as a lithium-ion secondary battery) have a discharge capacity of 97% or more of the rated capacity, it can be said to be in the state before degradation. The rated capacity of lithium-ion secondary batteries for portable devices complies with JIS C 8711:2019. For other lithium-ion secondary batteries, the rated capacity complies with not only the above JIS standard but also with each JIS, IEC standard, etc. for electric vehicle propulsion and industrial use.

[0040] In this specification, the state of the materials in a secondary battery before deterioration is referred to as an initial product or initial state, and the state after deterioration (the state when the secondary battery has a discharge capacity less than 97% of the rated capacity) may be referred to as a product in use or in use state, or a used product or used state.

[0041] (Embodiment 1) In this embodiment, a positive electrode active material 100 of one embodiment of the present invention will be described with reference to FIGS.

[0042] Fig. 3 is a cross-section of a positive electrode active material 100 of one embodiment of the present invention. As shown in Fig. 3, the positive electrode active material 100 has a surface portion 100a and an interior portion 100b. The boundary between the surface portion 100a and the interior portion 100b is indicated by a dashed line in Fig. 3. The positive electrode active material 100 has a layered rock-salt crystal structure belonging to the space group R-3m.

[0043] In this specification, the surface layer 100a of the positive electrode active material 100 refers to a region within 10 nm perpendicular or approximately perpendicular to the surface. The term "approximately perpendicular" refers to a region between 80° and 100°. Surfaces caused by cracks and / or fissures may also be called the surface. The surface layer 100a is synonymous with the surface vicinity, surface vicinity region, or shell.

[0044] The region deeper than the surface layer 100a of the positive electrode active material is referred to as the interior 100b, which is synonymous with the interior region, bulk, or core.

[0045] 1 and 2 are schematic diagrams illustrating the crystal structure of the inside 100b of a positive electrode active material 100 according to one embodiment of the present invention. In Fig. 1 and Fig. 2, black circles represent oxygen. Diamonds surrounding Mg, Co, and Ni indicate that these elements are located at octahedral positions coordinated with 6 oxygen atoms.

[0046] As shown in FIG. 1, most of the interior 100b of the positive electrode active material 100 has a layered rock-salt crystal structure, but some of it has clusters 110 with a rock-salt crystal structure. The rock-salt clusters 110 are preferably scattered throughout the interior 100b. The rock-salt clusters 110 preferably contain magnesium oxide. The compound contained in the clusters 110 is not limited to magnesium oxide as long as it has a rock-salt crystal structure. For example, the clusters 110 may contain cobalt (II) oxide. If the volume of the clusters 110 is too large, there is a risk that it will hinder charging and discharging, but if the volume is too small, it is difficult to obtain the effect of alleviating distortion of the crystal structure. For this reason, the clusters 100 are, for example, 0.5 nm 32nm or more 3 Less than 1 nm is preferable. 3 degree is preferred.

[0047] 2, it is more preferable that nickel exists around the cluster 110. The "around" here refers to a region within 1 nm outside the cluster 110.

[0048] The volume of a positive electrode active material having a layered rock-salt crystal structure changes with charging and discharging. For example, it is known that lithium cobalt oxide expands and contracts in the c-axis direction with the insertion and desorption of lithium. However, unlike lithium ions, magnesium ions in the rock-salt clusters 110 scattered in the interior 100b are difficult to move during charging and discharging, so the clusters 110 are difficult to move with charging and discharging. Therefore, it is considered that the clusters 110 have less or almost no volume change with charging and discharging than the layered rock-salt crystal structure. Therefore, a stable crystal structure can be maintained even in a charged state. By having the clusters 110 scattered in the interior 100b, it may be possible to suppress the volume change of the positive electrode active material 100 during charging and discharging. As a result, it is expected that the clusters 110 function as a stress relaxation region in the interior 100b of the positive electrode active material 100.

[0049] The positive electrode active material 100 having the clusters 110 is expected to have a crystal structure that is less likely to collapse, and is therefore expected to be more stable during charging and discharging at temperatures higher than room temperature, such as 40°C or even 60°C.

[0050] The rock-salt type clusters 110 can be observed, for example, from a STEM (Scanning Transmission Electron Microscope) image of the interior 100b of the positive electrode active material 100, electron diffraction, or the like.

[0051] If the rock salt type clusters 110 are too few, the stress relaxation function is not fully exerted, but if they are too many, the area contributing to charge and discharge in the positive electrode active material 100 is reduced. In order to keep the clusters 110 in a preferable range, the Mg / Co (atomic ratio) in the interior 100b is preferably 0.005 to 0.02, more preferably 0.01 to 0.02. Also, the Ni / Co is preferably 0.005 to 0.04, more preferably 0.01 to 0.02.

[0052] Furthermore, it is preferable that the number of magnesium atoms and the number of nickel atoms in the inner portion 100b are approximately the same, which means that the ratio of Mg / Ni (atomic number) is 0.8 or more and 1.2 or less.

[0053] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the surface layer portion 100a and the interior portion 100b. Therefore, the positive electrode active material 100 does not include metal oxides such as aluminum oxide (Al2O3) that do not have lithium sites that can contribute to charging and discharging, carbonates that are chemically adsorbed after the preparation of the positive electrode active material, hydroxyl groups, etc. The attached metal oxide refers to, for example, a metal oxide whose crystal structure does not match that of the interior portion 100b.

[0054] It also does not include electrolytes, organic solvents, binders, conductive materials, or compounds derived from these that are attached to the positive electrode active material 100.

[0055] Although not shown, the positive electrode active material 100 may have a crystal grain boundary. The crystal grain boundary refers to, for example, a portion where particles of the positive electrode active material 100 are adhered to each other, a portion where the crystal orientation changes inside the positive electrode active material 100, that is, a portion where the repetition of bright and dark lines in a STEM image or the like becomes discontinuous, a portion containing many crystal defects, a portion where the crystal structure is disordered, and the like. The crystal defect refers to a defect that can be observed in a cross-sectional TEM (transmission electron microscope) or a cross-sectional STEM image, that is, a structure in which other atoms have entered between lattices, a cavity, and the like. The crystal grain boundary can be said to be one of the plane defects. The vicinity of the crystal grain boundary refers to a region within 10 nm from the crystal grain boundary.

[0056] <Contained elements> The positive electrode active material 100 includes lithium, a transition metal M, oxygen, and an additive element. The transition metal M is at least one selected from cobalt, nickel, and manganese. Alternatively, the positive electrode active material 100 includes a composite oxide (LiMO2) of lithium and a transition metal M to which an additive element has been added. However, the positive electrode active material 100 according to one embodiment of the present invention may have any distribution or crystal structure of the additive element described below. Therefore, the composition is not strictly limited to Li:M:O=1:1:2 (atomic ratio).

[0057] The positive electrode active material of a lithium ion secondary battery needs to have a transition metal capable of oxidation and reduction in order to maintain charge neutrality even when lithium ions are inserted and removed. The positive electrode active material 100 of one embodiment of the present invention preferably uses cobalt as the transition metal M responsible for the oxidation and reduction reaction. If the positive electrode active material 100 contains 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more of cobalt among the transition metals contained therein, it is preferable because it has many advantages such as being relatively easy to synthesize, being easy to handle, and having excellent cycle characteristics.

[0058] In addition, when the transition metal M of the positive electrode active material 100 is 75 atomic % or more, preferably 90 atomic % or more, and more preferably 95 atomic % or more, the stability when a large amount of lithium is released by charging is superior to that of a composite oxide in which nickel, such as lithium nickel oxide (LiNiO2), accounts for the majority of the transition metal. This is thought to be because the influence of distortion due to the Jahn-Teller effect is smaller in cobalt than in nickel. The strength of the Jahn-Teller effect in transition metal compounds varies depending on the number of electrons in the d orbital of the transition metal. In layered rock salt type composite oxides in which low-spin nickel (III) in octahedral coordination accounts for the majority of the transition metal M, such as lithium nickel oxide, the influence of the Jahn-Teller effect is large, and distortion is likely to occur in the layer consisting of octahedrons of nickel and oxygen. Therefore, there is a growing concern that the crystal structure will collapse during the charge-discharge cycle. In addition, nickel ions are larger than cobalt ions and are close to the size of lithium ions. Therefore, in layered rock-salt complex oxides in which nickel accounts for the majority of the transition metal M, such as lithium nickel oxide, there is a problem in that cation mixing of nickel and lithium is likely to occur.

[0059] Furthermore, it is preferable that the positive electrode active material 100 contains a small amount of manganese, since this increases the initial charge / discharge capacity. For example, the weight of manganese contained in the positive electrode active material 100 is preferably 20 ppm or more and 3000 ppm or less, and more preferably 50 ppm or more and 600 ppm or less. In this case, if the ratio of cobalt to the transition metal M is 95 atomic % or more, it is possible to achieve both the effect of increasing the initial charge / discharge capacity due to manganese and the effect of being relatively easy to synthesize and handle due to cobalt, and having excellent cycle characteristics.

[0060] The additive elements contained in the positive electrode active material 100 are preferably one or more selected from magnesium, titanium, nickel, aluminum, fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, and beryllium.

[0061] That is, the positive electrode active material 100 can include lithium cobalt oxide doped with magnesium and titanium, lithium cobalt oxide doped with magnesium, titanium, and fluorine, lithium cobalt oxide doped with magnesium, nickel, aluminum, and titanium, lithium cobalt oxide doped with magnesium, nickel, aluminum, titanium, and fluorine, and the like.

[0062] The additive element is preferably dissolved in the positive electrode active material 100. Therefore, for example, when performing a line analysis by STEM-EDX, the depth at which the amount of the additive element detected increases is preferably located deeper than the depth at which the amount of the transition metal M detected increases, i.e., on the inner side of the positive electrode active material 100.

[0063] In this specification, the depth at which the amount of a certain element detected in a STEM-EDX line analysis increases refers to the depth at which measurement values ​​that can be determined to be not noise in terms of intensity, spatial resolution, etc., are successively obtained.

[0064] As described below, these additive elements further stabilize the crystal structure of the positive electrode active material 100. In this specification and the like, the additive element is synonymous with a mixture or a part of a raw material.

[0065] The additive element does not necessarily have to include magnesium, titanium, nickel, aluminum, fluorine, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, or beryllium.

[0066] 〔distribution〕 The positive electrode active material 100 has the above-mentioned additive element in the surface layer portion 100a. It is more preferable that the positive electrode active material 100 has a plurality of additive elements. It is preferable that the surface layer portion 100a has a higher concentration of one or more selected from the additive elements than the inner portion 100b. It is also preferable that the surface layer portion 100a has a higher detected amount of one or more selected from the additive elements than the inner portion 100b. It is also preferable that the one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient.

[0067] It is more preferable that the distribution of the positive electrode active material 100 differs depending on the added element. For example, it is more preferable that the depth of the peak of the detection amount in the surface layer portion from the surface or a reference point in EDX line analysis described later differs depending on the added element. The detection amount peak here refers to the maximum value of the detection amount at 50 nm or less from the surface of the surface layer portion 100a. The detection amount refers to, for example, the count in EDX line analysis.

[0068] In order to achieve the above effects, it is preferable that the concentration of at least magnesium, nickel, and titanium among the additive elements is higher in the surface layer 100a than in the interior 100b. Or, it is preferable that the amount of detection in the surface layer 100a is larger than the amount of detection in the interior 100b. Furthermore, it is preferable that the peak of the detection amount is in a region closer to the surface in the surface layer 100a. For example, it is preferable that the peak of the detection amount is on the surface or within 3 nm from the reference point. It is also preferable that the distributions of magnesium and nickel overlap. The peaks of the detection amounts of magnesium and nickel may be at the same depth, or the peak of magnesium may be closer to the surface, or the peak of nickel may be closer to the surface. The difference in depth between the peak of the detection amount of nickel and the peak of the detection amount of magnesium is preferably within 3 nm, and more preferably within 1 nm. It is also preferable that the half-width of the detection amount is narrow.

[0069] Furthermore, the amount of nickel detected in the interior 100b may be very small compared to the surface layer 100a, or may not be detected, or may be 1 atomic % or less.

[0070] Although not shown, it is preferable that the amount of fluorine detected in the surface layer 100a is greater than the amount of fluorine detected inside, as is the case with magnesium or nickel. It is also preferable that the surface layer 100a has a peak of the amount of fluorine detected in a region closer to the surface. For example, it is preferable that the peak of the amount of fluorine detected in the surface layer 100a is located on the surface or within 3 nm from the reference point. Similarly, it is preferable that the amount of titanium, silicon, phosphorus, boron and / or calcium detected in the surface layer 100a is greater than the amount of fluorine detected inside. It is also preferable that the peak of the amount of fluorine detected in the surface layer 100a is located on the surface. For example, it is preferable that the peak of the amount of fluorine detected in the surface layer 100a is located on the surface or within 3 nm from the reference point.

[0071] Of the additive elements, at least aluminum preferably has a peak of detection amount inside compared to magnesium and titanium. The distributions of magnesium and aluminum may overlap, but may not overlap much. The peak of detection amount of aluminum may be present in the surface layer portion 100a, or may be deeper than the surface layer portion 100a. For example, it is preferable that the peak is present in a region of 5 nm to 30 nm from the surface or the reference point toward the inside.

[0072] By distributing aluminum as described above, the layered rock-salt crystal structure of the positive electrode active material 100 can be more stabilized. For example, it is expected that the surface layer 100a of the positive electrode active material 100 is prevented from changing from the layered rock-salt crystal structure to the spinel crystal structure. The spinel crystal structure generated in the layered rock-salt crystal structure may move or expand due to the movement of the charge of the transition metal M. In addition, defects such as grain boundaries in the positive electrode active material 100 may become a diffusion path for lithium ions in the c-axis direction. Additive elements such as aluminum may be contained in the vicinity of the defects. In other words, it can be said that the presence of aluminum may make it easier for lithium ions to diffuse.

[0073] The reason why aluminum is distributed deeper into the material than magnesium or titanium is believed to be because the diffusion rate of aluminum is faster than that of magnesium or titanium. On the other hand, the amount of aluminum detected in the area closest to the surface is low, presumably because aluminum is more stable in areas where magnesium and other elements are not present than in areas where they are dissolved in high concentrations.

[0074] More specifically, in the region of the layered rock-salt type of space group R-3m or the cubic rock-salt type, where magnesium is dissolved at a high concentration, the distance between the cation and oxygen is longer than in the layered rock-salt type LiAlO2, making it difficult for aluminum to exist stably. + Mg 2+ The valence change due to substitution to Co 3+ From Co 2+ However, since Al can only be trivalent, it is thought that it is difficult for it to coexist with magnesium in the rock salt or layered rock salt structure.

[0075] Although not shown, it is preferable that manganese has a detection amount peak inside magnesium, similar to aluminum.

[0076] However, the additive element does not necessarily have to have the same concentration gradient or distribution throughout the entire surface layer portion 100a of the positive electrode active material 100.

[0077] The (001)-oriented surface of the positive electrode active material 100 may have a different distribution of additive elements from the other surfaces. For example, the (001)-oriented surface and its surface layer 100a may have a lower detection amount of one or more selected from additive elements compared to surfaces other than the (001)-oriented surface. Specifically, the detection amount of one or more of magnesium, nickel, and titanium may be low. Alternatively, the (001)-oriented surface and its surface layer 100a may have a peak of the detection amount of one or more selected from additive elements that is shallower from the surface compared to surfaces other than the (001)-oriented surface. Specifically, the detection amount peaks of magnesium, titanium, and aluminum may be shallower compared to other surfaces.

[0078] In the layered rock-salt crystal structure of R-3m, the cations are arranged parallel to the (001) plane. This means that the MO2 layers and lithium layers are alternately stacked parallel to the (001) plane. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane.

[0079] Since the MO2 layer is relatively stable, it is more stable for the surface of the positive electrode active material 100 to have a (001) orientation. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) plane.

[0080] On the other hand, the diffusion path of lithium ions is exposed on the surface other than the (001) orientation. Therefore, the surface and the surface layer 100a other than the (001) orientation are important regions for maintaining the diffusion path of lithium ions, and at the same time, they are regions from which lithium ions are first desorbed and are therefore prone to become unstable. Therefore, it is extremely important to reinforce the surface and the surface layer 100a other than the (001) orientation in order to maintain the crystal structure of the entire positive electrode active material 100.

[0081] Therefore, it is important that the positive electrode active material 100 of one embodiment of the present invention has an additive element on the surface other than the (001)-oriented surface and on the surface portion 100a thereof. On the other hand, the concentration of the additive element may be low on the (001)-oriented surface and on the surface portion 100a thereof, as described above.

[0082] In the manufacturing method described in the following embodiment, in which high-purity LiMO2 is manufactured, and then additive elements are mixed and heated, the additive elements spread mainly through the diffusion path of lithium ions, and therefore it is easy to make the distribution of the additive elements in the surface other than the (001) orientation and in the surface layer 100a thereof into a preferred range.

[0083] 〔magnesium〕 Magnesium is divalent, and magnesium ions are more stable at the lithium site than at the cobalt site in the layered rock-salt crystal structure, so they are more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site of the surface layer 100a makes it easier to maintain the layered rock-salt crystal structure. This is presumably because the magnesium present at the lithium site functions as a pillar supporting the MO2 layers. The presence of magnesium also makes it easier to maintain the Li x When x in CoO2 is, for example, 0.24 or less, the desorption of oxygen around magnesium can be suppressed. In addition, the presence of magnesium is expected to increase the density of the positive electrode active material 100. In addition, if the magnesium concentration in the surface layer portion 100a is high, it is expected that the corrosion resistance against hydrofluoric acid generated by decomposition of the electrolyte solution will be improved.

[0084] At an appropriate concentration, magnesium does not adversely affect the insertion and desorption of lithium during charging and discharging, and the above benefits can be enjoyed. However, excessive magnesium may adversely affect the insertion and desorption of lithium. Furthermore, the effect of stabilizing the crystal structure may be reduced. This is thought to be because magnesium enters the cobalt site in addition to the lithium site. In addition, unnecessary magnesium compounds (oxides, fluorides, etc.) that do not substitute for either the lithium site or the cobalt site may segregate on the surface of the positive electrode active material, and may become resistance components of the secondary battery. In addition, as the magnesium concentration of the positive electrode active material increases, the discharge capacity of the positive electrode active material may decrease. This is thought to be because too much magnesium enters the lithium site, reducing the amount of lithium that contributes to charging and discharging.

[0085] Therefore, it is preferable that the amount of magnesium contained in the entire positive electrode active material 100 is appropriate. For example, the number of magnesium atoms is preferably 0.002 to 0.06 times the number of cobalt atoms, more preferably 0.005 to 0.03 times, and even more preferably about 0.01 times. The amount of magnesium contained in the entire positive electrode active material 100 may be a value obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.

[0086] 〔nickel〕 In the layered rock salt crystal structure of LiMO2, nickel can exist in either the cobalt site or the lithium site. When nickel exists in the cobalt site, it has a lower redox potential than cobalt, so it is easier to release lithium and electrons during charging, for example. This is expected to result in faster charging and discharging speeds. Therefore, even with the same charging voltage, a larger charge and discharge capacity can be obtained when the transition metal M is nickel than when it is cobalt.

[0087] In addition, when nickel is present at the lithium site, the shift in the layered structure consisting of octahedra of cobalt and oxygen can be suppressed. The change in volume caused by charging and discharging is also suppressed. The elastic modulus also increases, that is, the material becomes harder. This is presumably because the nickel present at the lithium site also functions as a pillar supporting the MO2 layers. Therefore, it is expected that the crystal structure will become more stable, especially at high temperatures, for example, at 45°C or higher when the battery is in a charged state.

[0088] In addition, the distance between cations and anions in nickel oxide (NiO) is closer to the average distance between cations and anions in LiCoO2 than rock-salt MgO and rock-salt CoO, making it easier for the orientation to match that of LiCoO2.

[0089] In addition, the order of ionization tendency is lowest for magnesium, followed by aluminum, cobalt, and nickel (Mg>Al>Co>Ni). Therefore, nickel is thought to be less likely to dissolve into the electrolyte during charging than the other elements listed above. Therefore, it is thought to have a high effect of stabilizing the crystal structure of the surface layer when in a charged state.

[0090] Furthermore, nickel is Ni 2+ , Ni 3+ , Ni 4+ Of which, Ni 2+ is the most stable, and nickel has a higher trivalent ionization energy than cobalt. Therefore, it is known that nickel and oxygen alone do not form a spinel crystal structure. Therefore, nickel is thought to have the effect of suppressing the phase change from the layered rock salt type to the spinel type crystal structure.

[0091] On the other hand, an excess of nickel is undesirable because it increases the influence of distortion due to the Jahn-Teller effect, and too much nickel can also adversely affect the insertion and extraction of lithium.

[0092] Therefore, it is preferable that the amount of nickel contained in the entire positive electrode active material 100 is appropriate. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably more than 0 and 7.5% or less of the number of cobalt atoms, more preferably 0.05% or more and 4% or less, more preferably 0.1% or more and 2% or less, and more preferably 0.2% or more and 1% or less. Or, it is preferably more than 0 and 4% or less of the number of cobalt atoms. Or, it is preferably more than 0 and 2% or less of the number of cobalt atoms. Or, it is preferably 0.05% or more and 7.5% or less. Or, it is preferably 0.05% or more and 2% or less. Or, it is preferably 0.1% or more and 7.5% or less. Or, it is preferably 0.1% or more and 4% or less. The amount of nickel shown here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.

[0093] 〔aluminum〕 Aluminum can also be present at the cobalt site in the layered rock salt crystal structure. Aluminum is a typical trivalent element and its valence does not change, so lithium around the aluminum is less likely to move during charging and discharging. Therefore, aluminum and the lithium around it function as columns, and can suppress changes in the crystal structure. Therefore, as described below, even if the positive electrode active material 100 is subjected to a force that causes it to expand and contract in the c-axis direction due to the insertion and removal of lithium ions, that is, even if a force that causes it to expand and contract in the c-axis direction is applied by changing the charge depth or charge rate, deterioration of the positive electrode active material 100 can be suppressed.

[0094] Aluminum also has the effect of suppressing the dissolution of surrounding cobalt and improving the continuous charging resistance. Furthermore, since the Al-O bond is stronger than the Co-O bond, it is possible to suppress the desorption of oxygen from the surroundings of aluminum. These effects improve the thermal stability. Therefore, when aluminum is contained as an additive element, the safety of the positive electrode active material 100 when used in a secondary battery can be improved. Furthermore, the positive electrode active material 100 can be made to have a crystal structure that is less likely to collapse even when repeatedly charged and discharged.

[0095] On the other hand, an excess of aluminum may adversely affect the insertion and extraction of lithium.

[0096] Therefore, it is preferable that the amount of aluminum contained in the entire positive electrode active material 100 is appropriate. For example, the number of aluminum atoms contained in the entire positive electrode active material 100 is preferably 0.05% to 4% of the number of cobalt atoms, preferably 0.1% to 2% and more preferably 0.3% to 1.5%. Alternatively, 0.05% to 2% is preferable. Alternatively, 0.1% to 4% is preferable. The amount contained in the entire positive electrode active material 100 here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material 100 using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.

[0097] [Fluorine] Fluorine is a monovalent anion, and when part of the oxygen in the surface layer portion 100a is replaced by fluorine, the lithium desorption energy is reduced. This is because the redox potential of the cobalt ion accompanying lithium desorption differs depending on the presence or absence of fluorine. In other words, when there is no fluorine, the cobalt ion changes from trivalent to tetravalent as lithium desorption occurs. On the other hand, when there is fluorine, the cobalt ion changes from divalent to trivalent as lithium desorption occurs. The redox potential of the cobalt ion differs between the two. Therefore, when part of the oxygen in the surface layer portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the desorption and insertion of lithium ions near the fluorine easily occurs. Therefore, when the positive electrode active material 100 is used in a secondary battery, the charge / discharge characteristics, large current characteristics, etc. can be improved. In addition, the presence of fluorine in the surface layer portion 100a having a surface that is in contact with the electrolyte, or the attachment of fluoride to the surface, can suppress excessive reaction between the positive electrode active material 100 and the electrolyte. In addition, the corrosion resistance to hydrofluoric acid can be effectively improved.

[0098] In addition, when the melting point of the fluoride, such as lithium fluoride, is lower than that of the other additive element sources, it can function as a flux (also called a fluxing agent) that lowers the melting point of the other additive element sources. When the fluoride contains LiF and MgF2, since the eutectic point of LiF and MgF2 is around 742°C, it is preferable to set the heating temperature to 742°C or higher in the heating step after mixing the additive elements.

[0099] Here, the differential scanning calorimetry (DSC) measurement of the fluoride and the mixture will be described with reference to Fig. 4(A) and Fig. 4(B). The device and conditions for the DSC measurement are not particularly limited, but in this embodiment, the measurement was performed with the following device and conditions. DSC equipment: Rigaku, EVO2 DSC8271 Heating rate: 20℃ / min The measurement results were analyzed using the Thermo prus EVO software to perform background correction and estimate the initial melting temperature T im , melting peak temperature Tpm and the end of melting temperature T em The heat flow was calculated as the heat flow rate per sample weight.

[0100] Figure 4(A) shows the results of a DSC measurement of a mixture of lithium fluoride and magnesium fluoride as fluorides with a molar ratio of LiF:MgF2 = 1:3. Figure 4(B) shows the results of a DSC measurement of the mixture with lithium cobalt oxide (C-10N, manufactured by Nippon Chemical Industry Co., Ltd.) added. The mixture was mixed with a molar ratio of LiCoO2:LiF:MgF2 = 100:0.33:1.

[0101] As shown in FIG. 4(A), the initial melting temperature T im is 731℃, melting peak temperature T pm is 739℃, and the melting end temperature T em The T of the mixture of lithium cobalt oxide, lithium fluoride, and magnesium fluoride was 746°C. im is 779℃, T pm is 815℃, T em was 826°C.

[0102] Therefore, the heating temperature after mixing the additive element is preferably 731°C or higher, and more preferably 826°C or higher. It may also be 800°C or higher, which is between these temperatures. A higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and productivity is high, but if the temperature is too high, there is a risk of decomposition of lithium cobalt oxide. Therefore, the upper limit of the heating temperature is set to be lower than the decomposition temperature of lithium cobalt oxide (1130°C). At temperatures near the decomposition temperature, there is a concern that lithium cobalt oxide may decompose, although only in small amounts. Therefore, a temperature of 1000°C or lower is more preferable.

[0103] [Other additive elements] When phosphorus is present in the surface layer 100a, Li x When x in CoO2 is kept small, it is preferable because short circuits can be suppressed. For example, it is preferable that CoO2 exists in the surface layer portion 100a as a compound containing phosphorus and oxygen.

[0104] In the case where the positive electrode active material 100 contains phosphorus, it is possible that the hydrogen fluoride generated by decomposition of the electrolytic solution or electrolyte reacts with the phosphorus, thereby decreasing the hydrogen fluoride concentration in the electrolyte, which is preferable.

[0105] When the electrolyte contains LiPF6, hydrogen fluoride may be generated by hydrolysis. In addition, hydrogen fluoride may be generated by a reaction between polyvinylidene fluoride (PVDF), which is used as a component of the positive electrode, and an alkali. By reducing the hydrogen fluoride concentration in the electrolyte, corrosion of the current collector and / or peeling of the coating 104 may be suppressed. In addition, a decrease in adhesion due to gelation and / or insolubilization of PVDF may be suppressed.

[0106] When the positive electrode active material 100 contains phosphorus together with magnesium, Li x This is preferable because the stability is extremely high when x in CoO2 is small. When the positive electrode active material 100 contains phosphorus, the number of phosphorus atoms is preferably 1% to 20% of the number of cobalt atoms, more preferably 2% to 10%, and even more preferably 3% to 8%. Or preferably 1% to 10%. Or preferably 1% to 8%. Or preferably 2% to 20%. Or preferably 2% to 8%. Or preferably 3% to 20%. Or preferably 3% to 10%. In addition, the number of magnesium atoms is preferably 0.1% to 10% of the number of cobalt atoms, more preferably 0.5% to 5%, and more preferably 0.7% to 4%. Or preferably 0.1% to 5%. Or preferably 0.1% to 4%. Or preferably 0.5% to 10%. Or preferably 0.5% to 4%. Or preferably 0.7% to 10%. Alternatively, the phosphorus and magnesium concentrations shown here may be values ​​obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GD-MS, ICP-MS, or the like, or may be based on values ​​of the composition of raw materials in the process of producing the positive electrode active material 100.

[0107] Furthermore, when the positive electrode active material 100 has a crack, the progression of the crack can be suppressed by the presence of phosphorus, more specifically, a compound containing phosphorus and oxygen, inside the positive electrode active material with the crack on the surface, for example, in the embedded portion.

[0108] [Synergistic effect of multiple added elements] Furthermore, when the surface layer 100a contains both magnesium and nickel, there is a possibility that the divalent nickel can exist more stably near the divalent magnesium. x Even when x in MO2 is small, the elution of magnesium can be suppressed, which can contribute to the stabilization of the surface layer portion 100a.

[0109] For the same reason, in the manufacturing process, when adding an additive element to lithium cobalt oxide, it is preferable that magnesium is added in a process before nickel. Alternatively, it is preferable that magnesium and nickel are added in the same process. Magnesium has a large ionic radius and tends to remain in the surface layer of lithium cobalt oxide regardless of the process in which it is added, whereas nickel can diffuse widely inside lithium cobalt oxide in the absence of magnesium. Therefore, if nickel is added before magnesium, there is a concern that nickel will diffuse into the lithium cobalt oxide and will not remain in the surface layer in a desired amount.

[0110] Also, if the positive electrode active material 100 has additive elements with different distributions, it is preferable because it can stabilize the crystal structure in a wider region. For example, if the positive electrode active material 100 has both magnesium and nickel distributed in a region closer to the surface of the surface layer 100a and aluminum distributed in a region deeper than these, it can stabilize the crystal structure in a wider region than if it had only one of them. In this way, when the positive electrode active material 100 has additive elements with different distributions, aluminum is not essential for the surface because the stabilization of the surface can be sufficiently achieved by magnesium, nickel, etc. Rather, it is preferable that aluminum is widely distributed in a deeper region. For example, it is preferable that aluminum is continuously detected in a region from the surface to a depth of 1 nm to 25 nm. It is preferable that aluminum is widely distributed in a region from 0 nm to 100 nm from the surface, preferably from 0.5 nm to 50 nm from the surface, because it can stabilize the crystal structure in a wider region.

[0111] When a plurality of additive elements are contained as described above, the effects of the respective additive elements are synergistic and can contribute to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are contained, the effect of providing a stable composition and crystal structure is high, and this is preferable.

[0112] However, if the surface layer 100a is occupied only by a compound of the added element and oxygen, it is not preferable because it makes it difficult to insert and remove lithium. For example, it is not preferable for the surface layer 100a to be occupied only by MgO or a structure in which MgO and MO(II) (e.g., CoO(II)) are solid-solved. Therefore, the surface layer 100a must contain at least a transition metal M such as cobalt, and must also contain lithium in the discharged state, and must have a path for the insertion and removal of lithium.

[0113] In order to ensure sufficient paths for lithium insertion and desorption, it is preferable that the surface layer 100a has a higher cobalt concentration than magnesium. For example, when measured from the surface of the positive electrode active material 100 by XPS, the ratio Mg / Co of the number of magnesium atoms Mg to the number of cobalt atoms Co is preferably 0.62 or less. It is also preferable that the surface layer 100a has a higher cobalt concentration than nickel. It is also preferable that the surface layer 100a has a higher cobalt concentration than aluminum. It is also preferable that the surface layer 100a has a higher cobalt concentration than fluorine.

[0114] Furthermore, since too much nickel may hinder the diffusion of lithium, it is preferable that the surface layer portion 100a has a higher concentration of magnesium than nickel. For example, when measured from the surface of the positive electrode active material 100 by XPS, the number of nickel atoms is preferably 1 / 6 or less of the number of magnesium atoms.

[0115] In addition, it is preferable that some of the added elements, particularly magnesium, nickel and aluminum, have a higher concentration in the surface layer 100a than in the interior 100b, but it is also preferable that they are present randomly and dilutely in the interior 100b. When magnesium and aluminum are present at an appropriate concentration in the lithium site of the interior 100b, it has the effect of making it easier to maintain the layered rock-salt crystal structure as described above. When nickel is present at an appropriate concentration in the interior 100b, it is possible to suppress the deviation of the layered structure consisting of octahedra of cobalt and oxygen as described above. When magnesium and nickel are present together, a synergistic effect of suppressing the elution of magnesium can be expected as described above.

[0116] It is preferable that the crystal structure changes continuously from the inside 100b toward the surface due to the concentration gradient of the added element as described above, or that the crystal orientation of the surface layer portion 100a and the inside 100b is approximately the same.

[0117] For example, it is preferable that the crystal structure changes continuously from the inside 100b of the layered rock salt type toward the surface and surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type. It is also preferable that the orientation of the surface layer portion 100a having characteristics of the rock salt type or both the rock salt type and the layered rock salt type and the inside 100b of the layered rock salt type are approximately the same.

[0118] In this specification, the layered rock-salt type crystal structure belonging to the space group R-3m, which is possessed by a composite oxide containing lithium and a transition metal such as cobalt, refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Defects such as deficiencies of cations or anions may be present. Strictly speaking, the layered rock-salt type crystal structure may have a structure in which the lattice of the rock-salt type crystal is distorted.

[0119] The rock-salt crystal structure is a cubic crystal structure, such as that of the space group Fm-3m, in which cations and anions are arranged alternately. Note that cations or anions may be missing.

[0120] Moreover, the fact that it has both the characteristics of the layered rock salt type and the rock salt type crystal structure can be determined by electron diffraction, TEM images, cross-sectional STEM images, etc.

[0121] In the rock salt type, there is no distinction in the cation sites, but in the layered rock salt type, there are two types of cation sites in the crystal structure, one of which is mostly occupied by lithium and the other by a transition metal. The layered structure in which two-dimensional planes of cations and two-dimensional planes of anions are alternately arranged is the same for both the rock salt type and the layered rock salt type. Among the bright spots in the electron diffraction pattern corresponding to the crystal planes that form this two-dimensional plane, when the central spot (transmitted spot) is set as the origin 000, the bright spot closest to the central spot is, for example, the (111) plane in the ideal rock salt type, and, for example, the (003) plane in the layered rock salt type. For example, when comparing the electron diffraction patterns of rock salt type MgO and layered rock salt type LiCoO2, the distance between the bright spots on the (003) plane of LiCoO2 is observed to be about half the distance between the bright spots on the (111) plane of MgO. Therefore, if the analysis area contains two phases, for example, rock-salt MgO and layered rock-salt LiCoO2, the electron diffraction pattern will have a plane orientation in which bright spots of high brightness and bright spots of low brightness are arranged alternately. Bright spots common to both the rock-salt and layered rock-salt types will have high brightness, while bright spots occurring only in the layered rock-salt type will have low brightness.

[0122] Furthermore, when a layered rock-salt crystal structure is observed from a direction perpendicular to the c-axis in cross-sectional STEM images, layers observed with strong brightness and layers observed with weak brightness are observed alternating. This characteristic is not seen in the rock-salt type, as there is no distinction in the cation sites. In the case of a crystal structure that has characteristics of both the rock-salt type and the layered rock-salt type, when observed from a specific crystal orientation, layers observed with strong brightness and layers observed with weak brightness are observed alternating in cross-sectional STEM images, and furthermore, a metal with an atomic number higher than that of lithium is present in part of the weak brightness layer, i.e., the lithium layer.

[0123] Layered rock-salt crystals and the anions of rock-salt crystals have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions of the O3' type and monoclinic O1(15) crystals described below also have a cubic close-packed structure. Therefore, when a layered rock-salt crystal and a rock-salt crystal come into contact, there are crystal faces where the cubic close-packed structure composed of anions is aligned.

[0124] Alternatively, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock-salt type has a space group of R-3m and a rhombohedral structure, but to make the structure easier to understand, it is generally represented as a compound hexagonal lattice, and the (0001) plane of the layered rock-salt type has a hexagonal lattice. The triangular lattice of the cubic {111} plane has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock-salt type. When the two lattices are compatible, it can be said that the orientation of the cubic close-packed structure is aligned.

[0125] However, the space group of the layered rock salt crystal and O3' type crystal is R-3m, which is different from the space group Fm-3m (the space group of general rock salt crystals) of the rock salt crystal, so the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock salt crystal and O3' type crystal and the rock salt crystal. In this specification, when the orientation of the cubic close-packed structure formed by anions in the layered rock salt crystal, O3' type and rock salt crystal is aligned, it may be said that the crystal orientation is approximately the same. In addition, the three-dimensional structural similarity in which the crystal orientation is approximately the same, or the same crystallographic orientation, is called topotaxis.

[0126] The fact that the crystal orientations of the two regions roughly coincide can be determined from TEM (Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope) images, electron diffraction patterns, etc. It can also be determined from FFT patterns of TEM images and FFT patterns of STEM images, etc. Furthermore, XRD (X-ray Diffraction), electron diffraction, neutron diffraction, etc. can also be used as materials for determination.

[0127] An example of a TEM image in which the orientation of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly coincides is shown in Figure 5. Images reflecting the crystal structure can be obtained in TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc.

[0128] For example, in high-resolution TEM images, contrast originating from crystal planes is observed. When an electron beam is incident perpendicular to the c-axis of a layered rock-salt type composite hexagonal lattice, for example, the contrast originating from the (0003) plane is observed as a repetition of bright and dark bands (bright strips) due to the diffraction and interference of the electron beam. Therefore, a repetition of bright and dark lines is observed in the TEM image, and two bright lines (for example, the L shown in Figure 5) are observed. RS and L LRS ) is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal planes are roughly aligned, that is, that the crystal orientations are roughly aligned. Similarly, when the angle between the two dark lines is 5 degrees or less, or 2.5 degrees or less, it can be determined that the crystal orientations are roughly aligned.

[0129] In addition, in HAADF-STEM images, contrast proportional to the atomic number is obtained, and elements with higher atomic numbers are observed brighter. For example, in the case of layered rock-salt lithium cobalt oxide belonging to the space group R-3m, cobalt (atomic number 27) has the highest atomic number, so the electron beam is strongly scattered at the position of the cobalt atom, and the arrangement of the cobalt atoms is observed as a bright line or an arrangement of strongly bright dots. Therefore, when lithium cobalt oxide with a layered rock-salt crystal structure is observed perpendicular to the c-axis, the arrangement of the cobalt atoms is observed as a bright line or an arrangement of strongly bright dots perpendicular to the c-axis, and the arrangements of the lithium atoms and oxygen atoms are observed as dark lines or low-brightness areas. The same is true when lithium cobalt oxide has fluorine (atomic number 9) and magnesium (atomic number 12) as added elements.

[0130] Therefore, when bright and dark lines are repeatedly observed in two regions with different crystal structures in a HAADF-STEM image and the angle between the bright lines is 5 degrees or less or 2.5 degrees or less, it can be determined that the atomic arrangements are roughly the same, that is, the crystal orientations are roughly the same. Similarly, when the angle between the dark lines is 5 degrees or less or 2.5 degrees or less, it can also be determined that the crystal orientations are roughly the same.

[0131] In ABF-STEM, elements with smaller atomic numbers appear brighter; however, like HAADF-STEM, it is possible to obtain contrast according to the atomic number, and therefore it is possible to determine the crystal orientation in the same way as with HAADF-STEM images.

[0132] Figure 6(A) shows an example of a STEM image in which the orientations of the layered rock-salt crystal LRS and the rock-salt crystal RS roughly match. Figure 6(B) shows the FFT pattern of the region of the rock-salt crystal RS, and Figure 6(C) shows the FFT pattern of the region of the layered rock-salt crystal LRS. The composition, JCPDS card number, and the d-value and angle calculated from these are shown on the left of Figure 6(B) and Figure 6(C). The measured values ​​are shown on the right. The spot marked with O is the zeroth order diffraction.

[0133] The spot marked A in Figure 6(B) is due to the 11-1 reflection of the cubic crystal. The spot marked A in Figure 6(C) is due to the 0003 reflection of the layered rock salt type. From Figures 6(B) and 6(C), it can be seen that the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly aligned. In other words, it can be seen that the line passing through AO in Figure 6(B) is roughly parallel to the line passing through AO in Figure 6(C). Here, roughly aligned and roughly parallel means that the angle is 5 degrees or less, or 2.5 degrees or less.

[0134] In this way, in the FFT pattern and the electron diffraction pattern, when the orientation of the layered rock salt type crystal and the rock salt type crystal roughly coincides, the <0003> orientation of the layered rock salt type and the <11-1> orientation of the rock salt type may roughly coincide. In this case, it is preferable that these reciprocal lattice points are spot-like, that is, not continuous with other reciprocal lattice points. The fact that the reciprocal lattice points are spot-like and not continuous with other reciprocal lattice points means that the crystallinity is high.

[0135] In addition, when the orientation of the 11-1 reflection of the cubic crystal and the orientation of the 0003 reflection of the layered rock salt type are roughly the same as described above, depending on the incidence orientation of the electron beam, a spot not originating from the 0003 reflection of the layered rock salt type may be observed in a reciprocal lattice space different from the orientation of the 0003 reflection of the layered rock salt type. For example, the spot marked B in FIG. 6(C) is originating from the 1014 reflection of the layered rock salt type. This may be observed at an angle of 52° to 56° (i.e., ∠AOB is 52° to 56°) from the orientation of the reciprocal lattice point (A in FIG. 6(C)) originating from the 0003 reflection of the layered rock salt type, and at a position where d is 0.19 nm to 0.21 nm. Note that this index is an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 0003 and 1014 may be used.

[0136] Similarly, a spot not originating from the 11-1 reflection of a cubic crystal may be observed in a reciprocal lattice space different from the orientation where the 11-1 reflection of a cubic crystal is observed. For example, the spot marked B in FIG. 6(B) originates from the 200 reflection of a cubic crystal. This is a diffraction spot observed at an angle of 54° to 56° (i.e., ∠AOB is 54° to 56°) from the orientation of the reflection originating from the 11-1 of a cubic crystal (A in FIG. 6(B)). Note that this index is only an example, and does not necessarily have to be the same. For example, a reciprocal lattice point equivalent to 11-1 and 200 may be used.

[0137] It is known that the layered rock salt type positive electrode active material, including lithium cobalt oxide, is likely to have the (0003) plane and its equivalent plane, as well as the (10-14) plane and its equivalent plane as crystal planes. Therefore, for example, when observing the (0003) plane with a TEM or the like, first select a particle of the positive electrode active material in which a crystal plane expected to be the (0003) plane is observed with a SEM or the like, and then, for example, the particle of the positive electrode active material may be processed into a thin slice with a FIB (Focused Ion Beam) or the like so that the (0003) plane can be observed with an electron beam incident on [12-10] in a TEM or the like. When it is desired to determine the coincidence of the crystal orientation, it is preferable to slice the layered rock salt type so that the (0003) plane can be easily observed.

[0138] <Crystal structure> <Li x When x in MO2 is 1≫ The positive electrode active material 100 according to one embodiment of the present invention is in a discharged state, i.e., Li x When x=1 in MO2, it has a layered rock-salt type crystal structure belonging to the space group R-3m. The layered rock-salt type composite oxide has a high discharge capacity, has a two-dimensional lithium ion diffusion path, is suitable for lithium ion insertion / extraction reactions, and is excellent as a positive electrode active material for secondary batteries. Therefore, it is particularly preferable that the inner part 100b, which occupies most of the volume of the positive electrode active material 100, has a layered rock-salt type crystal structure. The layered rock-salt type crystal structure is shown in FIG. 7 with R-3m O3 attached. R-3m O3 has lattice constants a = 2.81610, b = 2.81610, c = 14.05360, α = 90.0000, β = 90.0000, γ = 120.0000, and the coordinates of lithium, cobalt, and oxygen in the unit cell are Li(0, 0, 0), Co(0, 0, 0.5), and O(0, 0, 0.23951) (Non-Patent Document 5).

[0139] On the other hand, the surface layer portion 100a of the positive electrode active material 100 according to one embodiment of the present invention preferably has a function of reinforcing the layered structure of the transition metal M and oxygen octahedrons in the inner portion 100b so that the layered structure is not broken even when lithium is removed from the positive electrode active material 100 by charging. Alternatively, the surface layer portion 100a preferably functions as a barrier film for the positive electrode active material 100. Alternatively, the surface layer portion 100a, which is the outer periphery of the positive electrode active material 100, preferably reinforces the positive electrode active material 100. The reinforcement here means suppressing structural changes in the surface layer portion 100a and the inner portion 100b of the positive electrode active material 100, such as oxygen elimination and / or deviation of the layered structure of the transition metal M and oxygen octahedrons. And / or means suppressing oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0140] Therefore, it is preferable that the surface layer portion 100a has a different crystal structure from the inner portion 100b. It is also preferable that the surface layer portion 100a has a composition and a crystal structure that are more stable at room temperature (25° C.) than the inner portion 100b. For example, it is preferable that at least a part of the surface layer portion 100a of the positive electrode active material 100 of one embodiment of the present invention has a rock-salt type crystal structure. Alternatively, it is preferable that the surface layer portion 100a has both a layered rock-salt type crystal structure and a rock-salt type crystal structure. Alternatively, it is preferable that the surface layer portion 100a has characteristics of both a layered rock-salt type crystal structure and a rock-salt type crystal structure.

[0141] The surface layer 100a is the region from which lithium ions are first released during charging, and is the region where the lithium concentration is likely to be lower than that of the interior 100b. In addition, the atoms on the surface of the particles of the positive electrode active material 100 that are in the surface layer 100a can be said to be in a state where some of the bonds are broken. Therefore, the surface layer 100a is likely to become unstable, and is the region where deterioration of the crystal structure is likely to begin. For example, if the crystal structure of the layered structure consisting of transition metal M and oxygen octahedra in the surface layer 100a is displaced, the effect will be linked to the interior 100b, causing the layered crystal structure in the interior 100b to also be displaced, leading to deterioration of the crystal structure of the entire positive electrode active material 100. On the other hand, if the surface layer 100a can be sufficiently stabilized, Li xEven when x in MO2 is small, for example, 0.24 or less, the layered structure of the transition metal M and oxygen octahedra in the inner portion 100b can be made less likely to break. Furthermore, the displacement of the layer of the transition metal M and oxygen octahedra in the inner portion 100b can be suppressed.

[0142] <Li x MO2 with small x≫ The positive electrode active material 100 according to one embodiment of the present invention has the above-described distribution of additive elements and / or crystal structure in a discharged state, and thus has a high degree of conductivity. x The crystal structure when x in MO2 is small is different from that of conventional positive electrode active materials. <x≦0.24をいうこととする。

[0143] Using Figs. 7 to 11, Li x The change in crystal structure accompanying the change in x in MO 2 will be described with comparison between a conventional positive electrode active material and the positive electrode active material 100 of one embodiment of the present invention.

[0144] The change in the crystal structure of a conventional positive electrode active material is shown in Figure 8. The conventional positive electrode active material shown in Figure 8 is lithium cobalt oxide (LiCoO2) that does not have any added elements. The change in the crystal structure of lithium cobalt oxide that does not have any added elements is described in Non-Patent Documents 1 to 3, etc.

[0145] Figure 8 shows R-3m O3 and Li x The crystal structure of lithium cobalt oxide with x=1 in CoO2 is shown. In this crystal structure, lithium occupies the octahedral site, and there are three CoO2 layers in the unit cell. For this reason, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer is an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the edges are shared to form a continuous plane. This is sometimes called a layer made of octahedra of cobalt and oxygen.

[0146] In addition, conventional lithium cobalt oxide is known to have a crystal structure that belongs to the monoclinic space group P2 / m when the symmetry of lithium increases when x is about 0.5. This structure has one CoO2 layer in the unit cell. Therefore, it is sometimes called O1 type or monoclinic O1 type.

[0147] When x=0, the positive electrode active material has a trigonal space group P-3m1 crystal structure, and there is also one CoO2 layer in the unit cell. Therefore, this crystal structure is sometimes called O1 type, or trigonal O1 type. In addition, the trigonal structure may be converted to a composite hexagonal lattice and called hexagonal O1 type.

[0148] Furthermore, when x=0.12, conventional lithium cobalt oxide has a crystal structure of space group R-3m. This structure can be said to be a structure in which a trigonal O1-type CoO2 structure and an R-3m O3-type LiCoO2 structure are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3-type crystal structure. Note that the actual insertion and desorption of lithium does not necessarily occur uniformly in the positive electrode active material, and the lithium concentration may become uneven, so that an H1-3-type crystal structure is experimentally observed from about x=0.25. In addition, in reality, the number of cobalt atoms per unit cell in the H1-3-type crystal structure is twice that of other structures. However, in FIG. 8 and other documents, in order to make it easier to compare with other crystal structures, the c-axis of the H1-3-type crystal structure is shown as 1 / 2 of the unit cell.

[0149] As an example of the H1-3 type crystal structure, as described in Non-Patent Document 3, the coordinates of cobalt and oxygen in the unit cell can be expressed as Co (0,0,0.42150±0.00016), O1 (0,0,0.27671±0.00045), and O2 (0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Which unit cell should be used to express the crystal structure of the positive electrode active material can be determined, for example, by Rietveld analysis of the XRD pattern. In this case, it is sufficient to adopt a unit cell with a small GOF (goodness of fit) value.

[0150] Li x When the battery is repeatedly charged and discharged such that x in CoO2 becomes 0.24 or less, conventional lithium cobalt oxide repeatedly undergoes a change in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 type crystal structure and the R-3m O3 structure in the discharged state.

[0151] However, these two crystal structures have a large misalignment of the CoO2 layer. As shown by the dotted line and arrow in Figure 8, in the H1-3 type crystal structure, the CoO2 layer is significantly misaligned from that of R-3m O3 in the discharged state. Such dynamic structural changes can have a negative effect on the stability of the crystal structure.

[0152] Furthermore, the difference in volume between these two crystal structures is large, so that, per the same number of cobalt atoms, the difference in volume between the H1-3 crystal structure and the discharged R-3m O3 crystal structure exceeds 3.5%, typically 3.9% or more.

[0153] In addition, the H1-3 crystal structure, which has continuous CoO2 layers like the trigonal O1 type, is likely to be unstable.

[0154] Therefore, when charging and discharging are repeated so that x is 0.24 or less, the crystal structure of conventional lithium cobalt oxide collapses. The collapse of the crystal structure causes a deterioration in cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.

[0155] On the other hand, in the positive electrode active material 100 according to one embodiment of the present invention shown in FIG. xThe change in crystal structure between the discharged state where x in MO2 is 1 and the state where x is 0.24 or less is smaller than that of conventional positive electrode active materials. More specifically, the deviation of the MO2 layer between the state where x is 1 and the state where x is 0.24 or less can be reduced. Also, the change in volume compared per cobalt atom can be reduced. Therefore, the positive electrode active material 100 of one embodiment of the present invention is unlikely to collapse in crystal structure even when charging and discharging to a value of x 0.24 or less are repeated, and excellent cycle characteristics can be achieved. In addition, the positive electrode active material 100 of one embodiment of the present invention is unlikely to collapse in crystal structure even when charging and discharging to a value of x 0.24 or less are repeated, and excellent cycle characteristics can be achieved. x When x in MO2 is 0.24 or less, the positive electrode active material 100 according to one embodiment of the present invention can have a more stable crystal structure than conventional positive electrode active materials. x When x in MO2 is kept at 0.24 or less, short circuits are unlikely to occur. In such a case, the safety of the secondary battery is further improved, which is preferable.

[0156] Li x 7 shows the crystal structures of the interior 100b of the positive electrode active material 100 when x in MO2 is 1, approximately 0.2, and approximately 0.15. The interior 100b occupies the majority of the volume of the positive electrode active material 100 and is the part that contributes greatly to charge and discharge, so it can be said that the displacement of the MO2 layer and changes in volume are the most problematic part.

[0157] When x=1, the positive electrode active material 100 has the same crystal structure of R-3m O3 as conventional lithium cobalt oxide.

[0158] However, the positive electrode active material 100 has a crystal structure different from that of conventional lithium cobalt oxide when x is 0.24 or less, for example, about 0.2 or about 0.15, in which case the lithium cobalt oxide has an H1-3 type crystal structure.

[0159] The positive electrode active material 100 according to one embodiment of the present invention when x=0.2 has a crystal structure belonging to the trigonal space group R-3m. The symmetry of the CoO2 layer is the same as that of O3. Therefore, this crystal structure is called an O3'-type crystal structure. This crystal structure is shown in FIG. 7 with R-3m O3'.

[0160] The O3' type crystal structure can show the coordinates of cobalt and oxygen in the unit cell within the range of Co(0,0,0.5), O(0,0,x), 0.20≦x≦0.25. The lattice constant of the unit cell is preferably 2.797≦a≦2.837(Å), more preferably 2.807≦a≦2.827(Å), typically a=2.817(Å). The c-axis is preferably 13.681≦c≦13.881(Å), more preferably 13.751≦c≦13.811(Å), typically c=13.781(Å).

[0161] Moreover, when x=0.15, the positive electrode active material 100 according to one embodiment of the present invention has a crystal structure belonging to the monoclinic space group P2 / m. In this case, one CoO2 layer exists in the unit cell. In addition, the amount of lithium present in the positive electrode active material 100 at this time is about 15 atomic % in the discharged state. Therefore, this crystal structure is called a monoclinic O1(15) type crystal structure. This crystal structure is shown in FIG. 7 with the P2 / m monoclinic O1(15) attached.

[0162] The monoclinic O1(15) crystal structure has the coordinates of cobalt and oxygen in the unit cell as follows: Co1(0.5,0,0.5), Co2(0,0.5,0.5), O1(X O1 ,0,Z O1 ), 0.23≦X O1 ≦0.24, 0.61≦Z O1 ≦0.65, O2(X O2 ,0.5,Z O2 ), 0.75≦X O2 ≦0.78, 0.68≦Z O2 The lattice constant of the unit cell is in the range of ≦0.71. a = 4.880 ± 0.05 Å, b = 2.817 ± 0.05 Å, c = 4.839 ± 0.05 Å, α=90°, β=109.6±0.1°, γ=90°.

[0163] It is possible to show the lattice constants of this crystal structure in the space group R-3m if a certain degree of error is allowed. In this case, the coordinates of cobalt and oxygen in the unit cell are Co(0,0,0.5), O(0,0,Z O ), 0.21≦Z O ≦0.23. The lattice constant of the unit cell is a = 2.817 ± 0.02 Å, c=13.68±0.1 Å.

[0164] In both the O3' and monoclinic O1(15) crystal structures, ions of cobalt, nickel, magnesium, etc. occupy 6-coordinate oxygen sites, although lighter elements such as lithium and magnesium may occupy 4-coordinate oxygen sites.

[0165] As shown by the dotted line in FIG. 7, there is almost no deviation in the CoO2 layer between R-3m O3 in the discharged state and O3' and the monoclinic O1(15) type crystal structure.

[0166] The difference in volume per the same number of cobalt atoms between R-3m O3 in a discharged state and the O3' type crystal structure is 2.5% or less, more specifically 2.2% or less, typically 1.8%.

[0167] The difference in volume per the same number of cobalt atoms between R-3m O3 in a discharged state and the monoclinic O1(15) type crystal structure is 3.3% or less, more specifically 3.0% or less, typically 2.5%.

[0168] Table 1 shows the difference in volume per cobalt atom between R-3m O3 in a discharged state, O3', monoclinic O1(15), H1-3 type, and trigonal O1. For the lattice constants of each crystal structure used in the calculation of Table 1, literature values ​​can be referred to for R-3m O3 and trigonal O1 in a discharged state (ICSD coll.code.172909 and 88721). For H1-3, Non-Patent Document 3 can be referred to. For O3' and monoclinic O1(15), they can be calculated from experimental values ​​of XRD.

[0169] [Table 1]

[0170] In this way, in the positive electrode active material 100 according to one embodiment of the present invention, Li x When x in MO2 is small, that is, when a large amount of lithium is released, the change in the crystal structure is suppressed more than in conventional positive electrode active materials. In addition, the change in volume is also suppressed when compared per the same number of cobalt atoms. Therefore, the crystal structure of the positive electrode active material 100 is not easily broken even when charging and discharging are repeated so that x is 0.24 or less. Therefore, the decrease in the charge and discharge capacity during the charge and discharge cycles of the positive electrode active material 100 is suppressed. In addition, since more lithium can be stably used than in conventional positive electrode active materials, the positive electrode active material 100 has a large discharge capacity per weight and per volume. Therefore, by using the positive electrode active material 100, a secondary battery with a high discharge capacity per weight and per volume can be manufactured.

[0171] The positive electrode active material 100 is Li x It has been confirmed that when x in MO2 is 0.15 or more and 0.24 or less, it may have an O3' type crystal structure, and it is presumed that even when x is more than 0.24 and 0.27 or less, it has an O3' type crystal structure. x It has been confirmed that when x in MO2 is greater than 0.1 and less than 0.2, typically between 0.15 and 0.17, it may have a monoclinic O1(15) type crystal structure. However, the crystal structure is Li xSince it is affected by not only x in MO2 but also the number of charge / discharge cycles, charge / discharge current, temperature, electrolyte, etc., it is not necessarily limited to the above range of x.

[0172] Therefore, the positive electrode active material 100 is Li x When x in MO2 is more than 0.1 and not more than 0.24, it may have only O3' type, may have only monoclinic O1(15) type, or may have both crystal structures. All of the particles in the interior 100b of the positive electrode active material 100 do not have to have O3' type and / or monoclinic O1(15) type crystal structures. It may contain other crystal structures, or may be partially amorphous.

[0173] Also Li x To make the x in MO2 small, it is generally necessary to charge it at a high charging voltage. x The state where x in MO2 is small can be said to be a state where the battery is charged at a high charging voltage. For example, when the battery is charged by CC / CV at a voltage of 4.6 V or more based on the potential of lithium metal in an environment of 25°C, the H1-3 type crystal structure appears in the conventional positive electrode active material. Therefore, a charging voltage of 4.6 V or more based on the potential of lithium metal can be said to be a high charging voltage. In this specification and the like, unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal.

[0174] Therefore, the positive electrode active material 100 of one embodiment of the present invention can be said to be preferable because it can maintain a crystal structure having the symmetry of R-3m O3 even when charged at a high charging voltage, for example, a voltage of 4.6 V or more at 25° C. In other words, it can be said to be preferable because it can adopt an O3'-type crystal structure when charged at a higher charging voltage, for example, a voltage of 4.65 V or more and 4.7 V or less at 25° C. In other words, it can be said to be preferable because it can adopt a monoclinic O1(15)-type crystal structure when charged at an even higher charging voltage, for example, a voltage of more than 4.7 V and 4.8 V or less at 25° C.

[0175] Even with the positive electrode active material 100, the H1-3 type crystal structure may be observed only when the charging voltage is further increased. As described above, the crystal structure is affected by the number of charge / discharge cycles, the charge / discharge current, the temperature, the electrolyte, and the like. Therefore, when the charging voltage is lower, for example, even when the charging voltage is 4.5 V or more and less than 4.6 V at 25° C., the positive electrode active material 100 of one embodiment of the present invention may have the O3′ type crystal structure. Similarly, when charging at a voltage of 4.65 V or more and 4.7 V or less at 25° C., the monoclinic O1(15) type crystal structure may be observed.

[0176] In addition, when graphite is used as the negative electrode active material in the secondary battery, the voltage of the secondary battery is lower than the above by the potential of the graphite. The potential of graphite is about 0.05 V to 0.2 V based on the potential of lithium metal. Therefore, in the case of a secondary battery using graphite as the negative electrode active material, the battery has the same crystal structure at a voltage obtained by subtracting the potential of graphite from the above voltage.

[0177] In addition, in the O3' and monoclinic O1(15) of FIG. 7, lithium is shown to exist at all lithium sites with equal probability, but this is not limited to this. It may exist biasedly at some lithium sites, or, for example, in the monoclinic O1(Li 0.5 The distribution of lithium can be analyzed, for example, by neutron diffraction.

[0178] It can also be said that the O3' and monoclinic O1(15) types have random lithium between the layers, but are similar to the CdCl2 type crystal structure. 0.06 Although the crystal structure is close to that when charged to NiO2, it is known that pure lithium cobalt oxide or layered rock salt type positive electrode active materials containing a large amount of cobalt do not usually adopt a CdCl2 type crystal structure.

[0179] <Grain Boundaries> It is more preferable that the additive element contained in the positive electrode active material 100 of one embodiment of the present invention is distributed as described above, and that at least a part of the additive element is unevenly distributed in and near the crystal grain boundaries.

[0180] In this specification and the like, uneven distribution refers to the concentration of an element in a certain region being different from that in other regions, and is synonymous with segregation, precipitation, non-uniformity, bias, or the presence of a mixture of areas with high concentration and areas with low concentration.

[0181] For example, the magnesium concentration at and near the grain boundaries of the positive electrode active material 100 is preferably higher than that at and near the grain boundaries in the interior 100b. The fluorine concentration at and near the grain boundaries is also preferably higher than that at and near the grain boundaries in the interior 100b. The nickel concentration at and near the grain boundaries is also preferably higher than that at and near the grain boundaries in the interior 100b. The aluminum concentration at and near the grain boundaries is also preferably higher than that at and near the grain boundaries in the interior 100b.

[0182] Grain boundaries are one type of planar defect. Therefore, like the particle surface, they are prone to become unstable and changes in the crystal structure are likely to occur. Therefore, if the concentration of added elements at and near the grain boundaries is high, changes in the crystal structure can be more effectively suppressed.

[0183] In addition, when the magnesium concentration and fluorine concentration are high at and near the grain boundary, even if cracks occur along the grain boundary of the positive electrode active material 100 of one embodiment of the present invention, the magnesium concentration and fluorine concentration are high near the surface caused by the cracks. Therefore, even in the positive electrode active material after the cracks have occurred, the corrosion resistance against hydrofluoric acid can be improved. In addition, even in the positive electrode active material after the cracks have occurred, the side reaction between the electrolyte and the positive electrode active material can be suppressed.

[0184] <Particle size> If the particle size of the positive electrode active material 100 of one embodiment of the present invention is too large, there are problems such as difficulty in diffusing lithium and excessive roughness of the surface of the active material layer when applied to a current collector. On the other hand, if the particle size is too small, problems such as excessive reaction with the electrolyte solution occur. Therefore, the median diameter (D50) is preferably 1 μm or more and 100 μm or less, more preferably 2 μm or more and 40 μm or less, and even more preferably 5 μm or more and 30 μm or less. Alternatively, 1 μm or more and 40 μm or less is preferable. Alternatively, 1 μm or more and 30 μm or less is preferable. Alternatively, 2 μm or more and 100 μm or less is preferable. Alternatively, 2 μm or more and 30 μm or less is preferable. Alternatively, 5 μm or more and 100 μm or less is preferable. Alternatively, 5 μm or more and 40 μm or less is preferable.

[0185] In addition, when particles having different particle sizes are mixed and used in the positive electrode, the electrode density can be increased, and a secondary battery with high energy density can be obtained, which is preferable. The positive electrode active material 100 having a relatively small particle size is expected to have high charge / discharge rate characteristics. The positive electrode active material 100 having a relatively large particle size is expected to have high charge / discharge cycle characteristics and to maintain a high discharge capacity.

[0186] <Analysis method> A certain positive electrode active material is Li x When x in MO2 is small, whether or not the positive electrode active material 100 according to one embodiment of the present invention has an O3′ type and / or monoclinic O1(15) type crystal structure can be determined by Li x This can be determined by analyzing a positive electrode having a positive electrode active material with a small x in MO2 using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc.

[0187] In particular, XRD is preferred in that it can analyze the symmetry of transition metals such as cobalt contained in the positive electrode active material with high resolution, can compare the degree of crystallinity and the orientation of the crystals, can analyze the periodic distortion of the lattice and the crystallite size, can obtain sufficient accuracy even when the positive electrode obtained by disassembling the secondary battery is measured as it is, etc. Among XRD, powder XRD can obtain diffraction peaks that reflect the crystal structure of the inside 100b of the positive electrode active material 100, which occupies most of the volume of the positive electrode active material 100.

[0188] When analyzing the crystallite size by powder XRD, it is preferable to perform the measurement while excluding the influence of orientation due to pressure, etc. For example, it is preferable to take out the positive electrode active material from the positive electrode obtained by disassembling a secondary battery, prepare a powder sample, and then perform the measurement.

[0189] As described above, the positive electrode active material 100 according to one embodiment of the present invention is Li x It is characterized by the fact that there is little change in the crystal structure when x in MO2 is 1 and when it is 0.24 or less. Materials in which the crystal structure that undergoes large changes when charged at high voltage accounts for 50% or more of the crystal structure are not desirable because they cannot withstand high-voltage charging and discharging.

[0190] It should also be noted that the addition of an additive element alone may not result in an O3' or monoclinic O1(15) crystal structure. For example, even if lithium cobalt oxide with magnesium and fluorine or lithium cobalt oxide with magnesium and aluminum has something in common, depending on the concentration and distribution of the additive element, Li x When x in MO2 is 0.24 or less, the O3' type and / or monoclinic O1(15) type crystal structure accounts for 60% or more, or the H1-3 type crystal structure accounts for 50% or more.

[0191] Furthermore, even in the positive electrode active material 100 of one embodiment of the present invention, an H1-3 type or trigonal O1 type crystal structure may be generated when x is too small, such as 0.1 or less, or under conditions where the charging voltage exceeds 4.9 V. Therefore, in order to determine whether or not the positive electrode active material 100 of one embodiment of the present invention is a material, analysis of the crystal structure, such as XRD, and information on the charging capacity or charging voltage, etc. are required.

[0192] However, when the positive electrode active material has a small x, its crystal structure may change when it is exposed to air. For example, the crystal structure may change from O3' type or monoclinic O1(15) type to H1-3 type. Therefore, it is preferable to handle all samples used for crystal structure analysis in an inert atmosphere such as an argon atmosphere.

[0193] Furthermore, whether or not the distribution of the additive elements in a certain positive electrode active material is in the state described above can be determined by analyzing it using, for example, XPS, energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.

[0194] The crystal structure of surface layer 100a, grain boundaries, and the like can be analyzed by electron diffraction or the like of a cross section of positive electrode active material 100.

[0195] ≪Charging method≫ For example, charging for determining whether a certain complex oxide is the positive electrode active material 100 of one embodiment of the present invention can be performed by preparing a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) with a lithium counter electrode and charging the coin cell.

[0196] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive material, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.

[0197] Lithium metal can be used for the counter electrode. When a material other than lithium metal is used for the counter electrode, the potential of the secondary battery is different from the potential of the positive electrode. Unless otherwise specified, the voltage and potential in this specification are the potential of the positive electrode.

[0198] The electrolyte used in the electrolytic solution is 1 mol / L lithium hexafluorophosphate (LiPF6), and the electrolytic solution can be a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of EC:DEC = 3:7, with 2 wt% vinylene carbonate (VC).

[0199] The separator can be a 25 μm thick porous polypropylene film.

[0200] The positive electrode can and the negative electrode can may be made of stainless steel (SUS).

[0201] The coin cell prepared under the above conditions is charged at an arbitrary voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V, or 4.8V). The charging method is not particularly limited as long as the charging can be performed at an arbitrary voltage for a sufficient time. For example, when charging by CCCV, the current in CC charging can be 20mA / g or more and 100mA / g or less. CV charging can be terminated at 2mA / g or more and 10mA / g or less. In order to observe the phase change of the positive electrode active material, it is desirable to charge at such a small current value. On the other hand, if the current does not become 2mA / g or more and 10mA / g or less even after CV charging for a long time, it is considered that the current is consumed not for charging the positive electrode active material but for decomposing the electrolyte, so CV charging may be terminated when a sufficient time has passed since the start. The sufficient time in this case can be, for example, 1.5 hours or more and 3 hours or less. The temperature is 25°C or 45°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere to remove the positive electrode, and a positive electrode active material with a desired charging capacity can be obtained. When various analyses are performed thereafter, it is preferable to seal the cell in an argon atmosphere in order to suppress reactions with external components. For example, XRD can be performed by sealing the cell in a sealed container in an argon atmosphere. In addition, it is preferable to quickly remove the positive electrode and subject it to analysis after charging is completed. Specifically, it is preferable to do so within 1 hour after charging is completed, and more preferably within 30 minutes.

[0202] In addition, when analyzing the crystal structure in the charged state after multiple charge / discharge cycles, the multiple charge / discharge conditions may be different from the above-mentioned charging conditions. For example, charging can be performed by constant current charging at a current value of 20 mA / g to 100 mA / g up to an arbitrary voltage (e.g., 4.6 V, 4.65 V, 4.7 V, 4.75 V, or 4.8 V), followed by constant voltage charging until the current value becomes 2 mA / g to 10 mA / g, and discharging can be performed by constant current discharging at 2.5 V and 20 mA / g to 100 mA / g.

[0203] Furthermore, when analyzing the crystal structure in the discharged state after multiple charge / discharge cycles, constant current discharge can be performed at, for example, 2.5 V and a current value of 20 mA / g or more and 100 mA / g or less.

[0204] <XRD> The XRD measurement apparatus and conditions are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. XRD equipment: Bruker AXS, D8 ADVANCE X-ray source:Cu Output: 40kV, 40mA Divergence angle: Div.Slit, 0.5° Detector: LynxEye Scan method: 2θ / θ continuous scan Measurement range (2θ): 15° to 90° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm The background and CuKα2 peaks were removed from the obtained XRD patterns using the analysis software DIFFRAC.EVA.

[0205] If the measurement sample is a powder, it can be set by placing it in a glass sample holder, sprinkling the sample on a greased silicone non-reflective plate, etc. If the measurement sample is a positive electrode, the positive electrode can be attached to the substrate with double-sided tape, and the positive electrode active material layer can be set to match the measurement surface required by the device.

[0206] The ideal powder XRD patterns calculated from the O3' type crystal structure, the monoclinic O1(15) type crystal structure, and the H1-3 type crystal structure model are shown in Figures 9, 10, 11(A), and 11(B). x The ideal XRD patterns calculated from the crystal structure of LiCoO2O3 with x=1 in MO2 and trigonal O1 with x=0 are also shown. Figures 11(A) and 11(B) show the XRD patterns of the O3' type crystal structure, monoclinic O1(15) type crystal structure, and H1-3 type crystal structure, with Figure 11(A) showing an enlarged view of the region where 2θ is in the range of 18° to 21°, and Figure 11(B) showing an enlarged view of the region where 2θ is in the range of 42° to 46°. The patterns of LiCoO2(O3) and CoO2(O1) were created using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA), from crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 4). The range of 2θ was 15° to 75°, Step size=0.01, and wavelength λ1=1.540562×10 -10 m and λ2 were not set, and monochromator was set to single. The pattern of the H1-3 type crystal structure was similarly created from the crystal structure information described in Non-Patent Document 3. The patterns of the O3' type and monoclinic O1(15) type crystal structures were estimated from the XRD pattern of the positive electrode active material of one embodiment of the present invention, and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and XRD patterns were created in the same manner as the others.

[0207] As shown in Figures 9, 11(A) and 11(B), in the O3' type crystal structure, diffraction peaks appear at 2θ = 19.25 ± 0.12° (19.13° or more and less than 19.37°) and 2θ = 45.47 ± 0.10° (45.37° or more and less than 45.57°).

[0208] In addition, in the monoclinic O1(15) crystal structure, diffraction peaks appear at 2θ = 19.47 ± 0.10° (19.37° to 19.57°) and 2θ = 45.62 ± 0.05° (45.57° to 45.67°).

[0209] However, as shown in Figures 10, 11(A) and 11(B), no peaks appear at these positions in the H1-3 type crystal structure and trigonal O1. x The appearance of peaks at 19.13° or more and less than 19.37° and / or 19.37° or more and 19.57° or less, and at least 45.37° or more and less than 45.57° and / or at least 45.57° or more and 45.67° or less when x in CoO2 is small can be said to be a characteristic of the positive electrode active material 100 of one embodiment of the present invention.

[0210] This can also be said to mean that in the positive electrode active material 100 of one embodiment of the present invention, the positions at which XRD diffraction peaks appear are close between the crystal structures where x = 1 and where x ≦ 0.24. More specifically, it can be said that the difference in 2θ between the main diffraction peaks appearing at 2θ of 42° or more and 46° or less in the crystal structures where x = 1 and x ≦ 0.24 is 0.7° or less, more preferably 0.5° or less.

[0211] The positive electrode active material 100 according to one embodiment of the present invention is Li x When x in CoO2 is small, it has O3'-type and / or monoclinic O1(15)-type crystal structure, but not all of the particles may have O3'-type and / or monoclinic O1(15)-type crystal structure. It may contain other crystal structures, or may be partially amorphous. However, when Rietveld analysis is performed on the XRD pattern, it is preferable that the O3'-type and / or monoclinic O1(15)-type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more. If the O3'-type and / or monoclinic O1(15)-type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more, it can be a positive electrode active material with sufficiently excellent cycle characteristics.

[0212] Similarly, when Rietveld analysis is performed, the H1-3 type and O1 type crystal structures are preferably 50% or less, more preferably 34% or less, and even more preferably substantially not observed.

[0213] Furthermore, even after 100 or more charge / discharge cycles from the start of measurement, when Rietveld analysis is performed, the O3' type and / or monoclinic O1(15) type crystal structure is preferably 35% or more, more preferably 40% or more, and even more preferably 43% or more.

[0214] The sharpness of the diffraction peaks in the XRD pattern indicates the high crystallinity. Therefore, it is preferable that each diffraction peak after charging is sharp, that is, the half-width is narrow. For example, it is preferable that the full width at half maximum is narrow. The half-width varies depending on the XRD measurement conditions and the value of 2θ, even for peaks generated from the same crystal phase. In the case of the above-mentioned measurement conditions, the full width at half maximum is preferably 0.2° or less, more preferably 0.15° or less, and even more preferably 0.12° or less, for example, in peaks observed at 2θ=43° or more and 46° or less. It is not necessary for all peaks to meet this requirement. If some peaks meet this requirement, it can be said that the crystallinity of the crystal phase is high. Such high crystallinity contributes to the stabilization of the crystal structure after charging sufficiently.

[0215] In addition, the crystallite size of the O3' type and monoclinic O1(15) crystal structures of the positive electrode active material 100 is reduced to only about 1 / 20 of that of LiCoO2(O3) in the discharged state. Therefore, even if the XRD measurement conditions are the same as those of the positive electrode before and after charging and discharging, the Li x When x in CoO2 is small, clear peaks of O3' and / or monoclinic O1(15) crystal structure can be confirmed. On the other hand, in conventional LiCoO2, even if some parts have a structure similar to O3' and / or monoclinic O1(15) crystal structure, the crystallite size becomes small and the peak becomes broad and small. The crystallite size can be calculated from the half-width of the XRD peak.

[0216] In the positive electrode active material 100 according to one embodiment of the present invention, as described above, it is preferable that the influence of the Jahn-Teller effect is small. As long as the influence of the Jahn-Teller effect is small, a transition metal such as nickel or manganese may be contained as an additive element in addition to cobalt.

[0217] For example, when the nickel concentration is 5% and 7.5%, the a-axis / c-axis tends to change significantly, and when the nickel concentration is 7.5%, the distortion of the a-axis becomes large. The distortion may be caused by the Jahn-Teller distortion of trivalent nickel. Therefore, it is preferable that nickel is less than 7.5 atomic % of the transition metal M contained in the positive electrode active material 100.

[0218] Furthermore, when the manganese concentration is 5% or more, the behavior of the change in lattice constant is different, suggesting that it does not follow Vegard's law. Therefore, among the transition metals M contained in the positive electrode active material 100, manganese is preferably 4 atomic % or less.

[0219] The above ranges of nickel concentration and manganese concentration do not necessarily apply to the surface layer portion 100a, that is, the concentrations in the surface layer portion 100a may be higher than the above ranges.

[0220] As a result of considering the above-mentioned preferable range of the lattice constant, it was found that in the positive electrode active material of one embodiment of the present invention, the layered rock-salt crystal structure of the positive electrode active material 100 in a state in which no charge / discharge is performed or in a discharged state, which can be estimated from the XRD pattern, has an a-axis lattice constant of 2.814 × 10 -10 m or larger, 2.817×10 -10 m and the c-axis lattice constant is 14.05×10 -10 m or larger, 14.07×10 -10 It has been found that the value is preferably smaller than m. The state in which charging and discharging are not performed may be, for example, the powder state prior to fabrication of the positive electrode of a secondary battery.

[0221] Alternatively, in the layered rock-salt crystal structure of the positive electrode active material 100 in a state where no charge or discharge is performed or in a discharged state, the value obtained by dividing the lattice constant of the a-axis by the lattice constant of the c-axis (a-axis / c-axis) is preferably greater than 0.20000 and smaller than 0.20049.

[0222] Alternatively, when XRD analysis is performed on the layered rock-salt crystal structure of the positive electrode active material 100 in a state where no charge or discharge is performed or in a discharged state, a first peak may be observed at 2θ of 18.50° or more and 19.30° or less, and a second peak may be observed at 2θ of 38.00° or more and 38.80° or less.

[0223] <XPS> In X-ray photoelectron spectroscopy (XPS), in the case of inorganic oxides, when monochromatic aluminum Kα rays are used as the X-ray source, it is possible to analyze a region from the surface to a depth of about 2 to 8 nm (usually 5 nm or less), so the concentration of each element can be quantitatively analyzed in a region about half the depth of the surface layer 100a. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is often about ±1 atomic %, with a lower limit of about 1 atomic %, depending on the element.

[0224] In the positive electrode active material 100 according to one embodiment of the present invention, the concentration of one or more selected from the additive elements is preferably higher in the surface layer portion 100a than in the interior portion 100b. This is synonymous with the fact that the concentration of one or more selected from the additive elements in the surface layer portion 100a is preferably higher than the average concentration of the entire positive electrode active material 100. Therefore, for example, it can be said that the concentration of one or more additive elements selected from the surface layer portion 100a measured by XPS or the like is preferably higher than the average concentration of the additive elements in the entire positive electrode active material 100 measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry). For example, it is preferable that the magnesium concentration of at least a part of the surface layer portion 100a measured by XPS or the like is higher than the average magnesium concentration of the entire positive electrode active material 100. It is also preferable that the nickel concentration of at least a part of the surface layer portion 100a is higher than the average nickel concentration of the entire positive electrode active material 100. It is also preferable that the aluminum concentration in at least a part of the surface layer portion 100a is higher than the average aluminum concentration in the entire positive electrode active material 100. It is also preferable that the fluorine concentration in at least a part of the surface layer portion 100a is higher than the average fluorine concentration in the entire positive electrode active material 100.

[0225] The surface and surface layer 100a of the positive electrode active material 100 according to one embodiment of the present invention do not include carbonates, hydroxyl groups, etc. that are chemically adsorbed after the preparation of the positive electrode active material 100. Also, the electrolyte, binder, conductive material, or compounds derived from these that are attached to the surface of the positive electrode active material 100 are not included. Therefore, when quantifying the elements contained in the positive electrode active material, correction may be made to exclude carbon, hydrogen, excess oxygen, excess fluorine, etc. that can be detected by surface analysis such as XPS. For example, XPS allows the types of bonds to be separated by analysis, and correction may be made to exclude C-F bonds derived from the binder.

[0226] Furthermore, before being subjected to various analyses, the sample such as the positive electrode active material and the positive electrode active material layer may be washed in order to remove the electrolyte, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material. At this time, lithium may dissolve in the solvent used for washing, but even in this case, the added element is unlikely to dissolve, and therefore the atomic ratio of the added element is not affected.

[0227] The concentration of the added element may be compared in terms of the ratio to cobalt. By using the ratio to cobalt, the influence of carbonates and the like chemically adsorbed after the preparation of the positive electrode active material can be reduced and comparison is preferably made. For example, the ratio of the number of magnesium atoms to the number of cobalt atoms, Mg / Co, as determined by XPS analysis, is preferably 0.4 to 1.5. On the other hand, the ratio of Mg / Co as determined by ICP-MS analysis is preferably 0.001 to 0.06.

[0228] Similarly, in the positive electrode active material 100, in order to secure a sufficient path for the insertion and desorption of lithium, it is preferable that the concentrations of lithium and cobalt in the surface layer portion 100a are higher than the concentrations of one or more additive elements selected from the additive elements contained in the surface layer portion 100a measured by XPS or the like. For example, it is preferable that the concentration of at least a part of cobalt in the surface layer portion 100a measured by XPS or the like is higher than the concentration of magnesium in at least a part of the surface layer portion 100a measured by XPS or the like. Similarly, it is preferable that the concentration of lithium is higher than the concentration of magnesium. It is also preferable that the concentration of cobalt is higher than the concentration of nickel. It is also preferable that the concentration of lithium is higher than the concentration of nickel. It is also preferable that the concentration of cobalt is higher than the concentration of aluminum. It is also preferable that the concentration of lithium is higher than the concentration of aluminum. It is also preferable that the concentration of cobalt is higher than the concentration of fluorine. It is also preferable that the concentration of lithium is higher than the concentration of fluorine.

[0229] Furthermore, it is more preferable that aluminum is widely distributed in a deep region, for example, the surface, or a region having a depth of 5 nm to 50 nm from the reference point. Therefore, although aluminum is detected in the analysis of the entire positive electrode active material 100 using ICP-MS, GD-MS, etc., it is more preferable that the concentration of aluminum is not detected by XPS, etc., or is 1 atomic % or less.

[0230] Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is subjected to XPS analysis, the number of magnesium atoms is preferably 0.4 times or more and 1.2 times or less, more preferably 0.65 times or more and 1.0 times or less, relative to the number of cobalt atoms. The number of nickel atoms is preferably 0.15 times or less, more preferably 0.03 times or more and 0.13 times or less, relative to the number of cobalt atoms. The number of aluminum atoms is preferably 0.12 times or less, more preferably 0.09 times or less, relative to the number of cobalt atoms. The number of fluorine atoms is preferably 0.3 times or more and 0.9 times or less, more preferably 0.1 times or more and 1.1 times or less, relative to the number of cobalt atoms. The above ranges indicate that these additive elements are not attached to a narrow range on the surface of the positive electrode active material 100, but are widely distributed in a preferred concentration in the surface layer portion 100a of the positive electrode active material 100.

[0231] When performing XPS analysis, for example, monochromated aluminum Kα rays can be used as the X-ray source. The take-off angle can be set to, for example, 45°. For example, the measurement can be performed using the following equipment and conditions. Measurement equipment: PHI Quantera II X-ray source: Monochromatic Al Kα (1486.6eV) Detection area: 100μmφ Detection depth: Approx. 4 to 5 nm (take-off angle 45°) Measurement spectrum: Wide scan, narrow scan of each detected element

[0232] Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is analyzed by XPS, the peak indicating the bond energy between fluorine and other elements is preferably equal to or greater than 682 eV and less than 685 eV, and more preferably about 684.3 eV, which is a different value from both the bond energy of lithium fluoride (685 eV) and the bond energy of magnesium fluoride (686 eV).

[0233] Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is subjected to XPS analysis, the peak showing the bond energy between magnesium and other elements is preferably equal to or greater than 1302 eV and less than 1304 eV, and more preferably about 1303 eV, which is a different value from the bond energy of magnesium fluoride, 1305 eV, and is close to the bond energy of magnesium oxide.

[0234] <EDX> It is preferable that one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient. It is more preferable that the depth from the surface of the concentration peak differs depending on the additive element in the positive electrode active material 100. The concentration gradient of the additive element can be evaluated, for example, by exposing a cross section of the positive electrode active material 100 using a focused ion beam (FIB) or the like and analyzing the cross section using energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.

[0235] Among EDX measurements, EDX area analysis is performed by scanning an area and evaluating the area in two dimensions. EDX line analysis is performed by scanning a line and evaluating the distribution of atomic concentration within the positive electrode active material. Line analysis may also be used to extract data from a linear area of ​​EDX area analysis. Point analysis is used to measure an area without scanning it.

[0236] By EDX surface analysis (e.g., element mapping), the concentration of the added element can be quantitatively analyzed in the surface layer 100a, the inside 100b, and the vicinity of the grain boundary of the positive electrode active material 100. In addition, the concentration distribution and maximum value of the added element can be analyzed by EDX line analysis. In addition, analysis using a thinned sample such as STEM-EDX is more suitable because it can analyze the concentration distribution in the depth direction from the surface to the center of the positive electrode active material in a specific region without being affected by the distribution in the depth direction.

[0237] Since the positive electrode active material 100 is a compound containing oxygen and a transition metal capable of inserting and removing lithium, the interface between a region where the transition metal M (one or more selected from Co, Ni, and Mn) that is oxidized and reduced with the insertion and removal of lithium and oxygen is present and a region where they are not present is defined as the surface of the positive electrode active material. When the positive electrode active material is subjected to analysis, a protective film may be attached to the surface, but the protective film is not included in the positive electrode active material. As the protective film, a single layer film or a multilayer film of carbon, metal, oxide, resin, etc. may be used.

[0238] In STEM-EDX line analysis, the element profile does not change sharply in principle or due to measurement errors, and it may be difficult to precisely determine the surface. Therefore, when referring to the depth direction in STEM-EDX line analysis, the detection amount of the characteristic X-ray of the transition metal M is set as a reference point to be the average value M of the detection amount of the characteristic X-ray of the internal transition metal M. AVE and the average amount of characteristic X-rays of the transition metal M in the background, M BG The point where the amount of oxygen characteristic X-rays detected is 50% of the sum of the amount of oxygen characteristic X-rays detected inside the sample, or the amount of oxygen characteristic X-rays detected inside the sample is the average amount of oxygen characteristic X-rays detected inside the sample. AVE and the average amount of oxygen characteristic X-rays detected in the background, O BGNote that, if the point at which the detection amount of the characteristic X-rays of the transition metal M becomes 50% of the sum of the average detection amount of the characteristic X-rays of the transition metal M inside and the average detection amount of the characteristic X-rays of the transition metal M in the background is different from the point at which the detection amount of the characteristic X-rays of oxygen becomes 50% of the sum of the average detection amount of the characteristic X-rays of oxygen inside and the average detection amount of the characteristic X-rays of oxygen in the background, this is considered to be due to the influence of metal oxides, carbonates, etc. containing oxygen attached to the surface, so it is considered that the detection amount of the characteristic X-rays of the transition metal M becomes 50% of the sum of the average detection amount of the characteristic X-rays of the transition metal M inside AVE and the average amount of characteristic X-rays of the transition metal M in the background, M BG The reference point can be the point where the sum of the transition metals M and the transition metals M is 50% of the sum of the transition metals M and M. AVE and M BG The reference point can be found using:

[0239] The average background value of the transition metal M BG can be obtained by averaging, for example, a range of 2 nm or more, preferably 3 nm or more, from the outside of the positive electrode active material, avoiding the vicinity where the amount of detected transition metal M starts to increase. AVE can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, at a depth of 30 nm or more, preferably 50 nm or more, from the region where the counts of the transition metal M and oxygen are saturated and stable, for example, the region where the detected amount of the transition metal M starts to increase. BG and the average internal detection amount of oxygen, O AVE can also be found in the same way.

[0240] The surface of the positive electrode active material 100 in a cross-sectional STEM (scanning transmission electron microscope) image or the like is the boundary between an area where an image derived from the crystal structure of the positive electrode active material is observed and an area where it is not observed, and is the outermost area where an atomic column derived from the atomic nucleus of a metal element having a larger atomic number than lithium among the metal elements constituting the positive electrode active material is confirmed. Alternatively, it is the intersection point of a tangent drawn to a brightness profile from the surface to the bulk in a STEM image and an axis in the depth direction. The surface in a STEM image or the like may be determined in conjunction with an analysis with higher spatial resolution.

[0241] In addition, the spatial resolution of STEM-EDX is about 1 nm. Therefore, the maximum value of the additive element profile may deviate by about 1 nm. For example, even if the maximum value of the additive element profile of magnesium or the like is outside the surface obtained above, it can be considered an error as long as the difference between the maximum value and the surface is less than 1 nm.

[0242] In addition, a peak in STEM-EDX line analysis refers to the detected intensity in each element profile or the maximum value of the characteristic X-rays for each element. Note that noise in STEM-EDX line analysis can be considered to be a measurement value with a half-width less than the spatial resolution (R), for example, R / 2 or less.

[0243] The effect of noise can be reduced by scanning the same location multiple times under the same conditions. For example, the integrated values ​​measured over six scans can be used as the profile for each element. The number of scans is not limited to six, and it is also possible to perform more than six scans and use the average as the profile for each element.

[0244] The STEM-EDX line analysis can be carried out, for example, as follows: First, a protective film is deposited on the surface of the positive electrode active material. For example, carbon can be deposited using an ion sputtering device (MC1000 manufactured by Hitachi High-Technologies).

[0245] Next, the positive electrode active material is sliced ​​to prepare a STEM cross-section sample. For example, the slice processing can be performed using a FIB-SEM device (Hitachi High-Tech XVision200TBS). In this case, the pickup is performed using an MPS (micro-probing system), and the finishing processing conditions can be, for example, an acceleration voltage of 10 kV.

[0246] For STEM-EDX analysis, for example, a STEM device (Hitachi High-Tech HD-2700) can be used, and an EDAX Octane T Ultra W (two-wire) EDX detector can be used. During EDX analysis, the emission current of the STEM device is set to 6 μA or more and 10 μA or less, and a portion of the sliced ​​sample with minimal depth and unevenness is measured. The magnification is, for example, about 150,000 times. The conditions for EDX analysis can be drift correction, line width 42 nm, pitch 0.2 nm, and frame number 6 or more.

[0247] When EDX areal analysis or EDX point analysis is performed on positive electrode active material 100 of one embodiment of the present invention, it is preferable that the concentration of each additional element, particularly additional element X, in surface layer portion 100a is higher than that in interior portion 100b.

[0248] For example, when EDX surface analysis or EDX point analysis is performed on a positive electrode active material 100 having magnesium as an additive element, the magnesium concentration in the surface layer 100a is preferably higher than the magnesium concentration in the interior 100b. When EDX line analysis is performed, the peak of the magnesium concentration in the surface layer 100a is preferably present on the surface of the positive electrode active material 100 or at a depth of 3 nm from the reference point toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. The magnesium concentration is preferably attenuated to 60% or less of the peak at a point 1 nm deep from the peak top. It is also preferable that the magnesium concentration is attenuated to 30% or less of the peak at a point 2 nm deep from the peak top. The peak of concentration here refers to the maximum value of the concentration.

[0249] Furthermore, when EDX line analysis is performed, the magnesium concentration in the surface layer portion 100a (detected amount of magnesium / (sum of detected amounts of magnesium, oxygen, cobalt, fluorine, aluminum, and silicon) is preferably 0.5 atomic % or more and 10 atomic % or less, and more preferably 1 atomic % or more and 5 atomic % or less.

[0250] In the positive electrode active material 100 having magnesium and fluorine as additive elements, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the peak of the fluorine concentration and the peak of the magnesium concentration is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.

[0251] In addition, when EDX analysis is performed, the fluorine concentration peak of the surface layer 100a is preferably present on the surface of the positive electrode active material 100 or at a depth of 3 nm from the reference point toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Furthermore, if the fluorine concentration peak is slightly closer to the surface than the magnesium concentration peak, it is more preferable because it increases resistance to hydrofluoric acid. For example, it is more preferable that the fluorine concentration peak is 0.5 nm or more closer to the surface than the magnesium concentration peak, and even more preferable that it is 1.5 nm or more closer to the surface.

[0252] In the positive electrode active material 100 having nickel as an additive element, the nickel concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface or reference point of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. In the positive electrode active material 100 having magnesium and nickel, the nickel distribution is preferably superimposed on the magnesium distribution. For example, the difference in the depth direction between the nickel concentration peak and the magnesium concentration peak is preferably within 3 nm, more preferably within 1 nm.

[0253] Furthermore, when the positive electrode active material 100 contains aluminum as an added element, it is preferable that the peak of the magnesium, nickel, or fluorine concentration is closer to the surface than the peak of the aluminum concentration in the surface layer portion 100a when EDX line analysis is performed. For example, the peak of the aluminum concentration is preferably present on the surface of the positive electrode active material 100, or at a depth of 0.5 nm to 50 nm from the reference point toward the center, and more preferably at a depth of 5 nm to 50 nm.

[0254] In addition, when EDX line analysis, surface analysis, or point analysis is performed on the positive electrode active material 100, the ratio of the number of atoms of magnesium Mg and cobalt Co (Mg / Co) at the peak of magnesium concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.4. The ratio of the number of atoms of aluminum Al and cobalt Co (Al / Co) at the peak of aluminum concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.45. The ratio of the number of atoms of nickel Ni and cobalt Co (Ni / Co) at the peak of nickel concentration is preferably 0 to 0.2, more preferably 0.01 to 0.1. The ratio of the number of atoms of fluorine F and cobalt Co (F / Co) at the peak of fluorine concentration is preferably 0 to 1.6, more preferably 0.1 to 1.4.

[0255] Furthermore, when the positive electrode active material 100 is subjected to a line analysis or an area analysis, the ratio of the number of atoms of the additive element A to the cobalt Co in the vicinity of the grain boundaries (A / Co) is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. Still more preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 0.020 or more and 0.30 or less. Or it is preferably 0.020 or more and 0.20 or less. Or it is preferably 0.025 or more and 0.50 or less. Or it is preferably 0.025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less.

[0256] For example, when the additive element is magnesium, when the positive electrode active material 100 is subjected to a line analysis or a surface analysis, the ratio of the number of magnesium atoms to the number of cobalt atoms (Mg / Co) in the vicinity of the grain boundary is preferably 0.020 or more and 0.50 or less. More preferably, it is 0.025 or more and 0.30 or less. More preferably, it is 0.030 or more and 0.20 or less. Or it is preferably 0.020 or more and 0.30 or less. Or it is preferably 0.020 or more and 0.20 or less. Or it is preferably 0.025 or more and 0.50 or less. Or it is preferably 0.025 or more and 0.20 or less. Or it is preferably 0.030 or more and 0.50 or less. Or it is preferably 0.030 or more and 0.30 or less. If the ratio is within the above range at a plurality of locations, for example, three or more locations, of the positive electrode active material 100, it can be said that the additive element is not attached to a narrow range on the surface of the positive electrode active material 100, but is widely distributed at a preferred concentration in the surface layer portion 100a of the positive electrode active material 100.

[0257] EPMA EPMA (Electron Probe Microanalysis) can also quantify elements. Area analysis can analyze the distribution of each element.

[0258] When the cross section of the positive electrode active material 100 according to one embodiment of the present invention is subjected to EPMA surface analysis, it is preferable that one or more selected from the additive elements have a concentration gradient, as in the EDX analysis results. It is more preferable that the depth of the concentration peak from the surface differs depending on the additive element. The preferable range of the concentration peak of each additive element is also the same as in the case of EDX.

[0259] However, EPMA analyzes the region from the surface to a depth of about 1 μm. Therefore, the quantitative values ​​of each element may differ from the measurement results obtained by other analytical methods. For example, when the surface analysis of the positive electrode active material 100 is performed by EPMA, the concentration of each added element present in the surface layer 100a may be lower than the result of XPS.

[0260] <Raman spectroscopy> As described above, it is preferable that at least a part of the surface layer portion 100a of the positive electrode active material 100 of one aspect of the present invention has a rock salt-type crystal structure. Therefore, when the positive electrode active material 100 and the positive electrode having the same are analyzed by Raman spectroscopy, it is preferable that a crystal structure of a cubic system including a rock salt type as well as a crystal structure of layered rock salt is observed. In the STEM image and the selected area electron diffraction pattern described later, cobalt substituted at the lithium position with a certain frequency in the depth direction at the time of observation, and cobalt present at the oxygen four-coordination position, etc. cannot be detected as bright spots in the STEM image and the selected area electron diffraction pattern. On the other hand, since Raman spectroscopy is an analysis that captures the vibration mode of bonds such as Co-O, even when the abundance of the corresponding Co-O bond is small, peaks of the wave numbers of the corresponding vibration modes may be observed. Furthermore, Raman spectroscopy can measure a range of several μm in area and about 1 μm in depth of the surface layer portion, so that a state existing only on the particle surface can be captured with high sensitivity. 2 , and since it can measure a range of about 1 μm in depth, it can sensitively capture the state existing only on the particle surface.

[0261] For example, when the laser wavelength is 532 nm, in layered rock salt-type LiCoO2, peaks (vibration modes: E -1 , A -1 ) are observed at 470 cm -1 to 490 cm -1 , and at 580 cm g to 600 cm 1g . On the other hand, in cubic CoO x (0 < x < 1) (rock salt-type Co 1-y O(0 < y < 1) or spinel-type Co3O4), a peak (vibration mode: A -1 ) is observed at 665 cm -1 to 685 cm 1g .

[0262] Therefore, the integrated intensity of each peak is defined as I1 for 470 cm -1 to 490 cm -1 , I2 for 580 cm -1 to 600 cm -1 , and I3 for 665 cm -1 to 685 cm -1When I3 is taken as I3, the value of I3 / I2 is preferably 1% or more and 10% or less, and more preferably 3% or more and 9% or less.

[0263] When a cubic crystal structure such as a rock-salt type is observed in the above range, it can be said that surface layer portion 100a of positive electrode active material 100 has a rock-salt type crystal structure in a preferred range.

[0264] <Microelectron diffraction pattern> As in Raman spectroscopy, it is preferable that the characteristics of the rock salt type crystal structure are observed in the microelectron diffraction pattern as well as the layered rock salt crystal structure. However, in the STEM image and the microelectron diffraction pattern, taking into consideration the above-mentioned difference in sensitivity, it is preferable that the characteristics of the rock salt type crystal structure are not too strong in the surface layer 100a, especially in the outermost surface (for example, 1 nm deep from the surface). This is because the lithium layer can secure a diffusion path for lithium and have a stronger function of stabilizing the crystal structure if an additive element such as magnesium is present in the lithium layer while maintaining the layered rock salt type crystal structure, rather than the outermost surface being covered with a rock salt type crystal structure.

[0265] Therefore, for example, when a micro-electron diffraction pattern of a region having a depth of 1 nm or less from the surface and a micro-electron diffraction pattern of a region having a depth of 3 nm to 10 nm are obtained, it is preferable that the difference in lattice constant calculated from these patterns be small.

[0266] For example, the difference in lattice constant calculated from a measurement point at a depth of 1 nm or less from the surface and a measurement point at a depth of 3 nm to 10 nm is preferably 0.1 Å or less for the a-axis and 1.0 Å or less for the c-axis, more preferably 0.05 Å or less for the a-axis and more preferably 0.6 Å or less for the c-axis, even more preferably 0.04 Å or less for the a-axis and even more preferably 0.3 Å or less for the c-axis.

[0267] <Surface roughness and specific surface area> The positive electrode active material 100 according to one embodiment of the present invention preferably has a smooth surface with few irregularities. A smooth surface with few irregularities indicates that the effect of the flux described below is sufficiently exerted and the surfaces of the additive element source and the lithium cobalt oxide are melted. Therefore, this is one factor indicating that the distribution of the additive element in the surface layer portion 100a is good.

[0268] Whether the surface is smooth and has few projections and recesses can be determined, for example, from a cross-sectional SEM image or cross-sectional TEM image of the positive electrode active material 100, the specific surface area of ​​the positive electrode active material 100, or the like.

[0269] For example, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 as follows.

[0270] First, the cathode active material 100 is processed by FIB or the like to expose the cross section. At this time, it is preferable to cover the cathode active material 100 with a protective film, a protective agent, or the like. Next, an SEM image of the interface between the protective film or the like and the cathode active material 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, Gaussian blurring (σ=2) is performed, and then binarization is performed. Furthermore, interface extraction is performed using image processing software. Furthermore, the interface line between the protective film or the like and the cathode active material 100 is selected using an automatic selection tool or the like, and data is extracted to a spreadsheet software or the like. Using the functions of the spreadsheet software or the like, correction is performed from a regression curve (quadratic regression), and a parameter for calculating roughness is obtained from the data after the slope correction, and the root mean square surface roughness (RMS) is calculated by calculating the standard deviation. In addition, this surface roughness is the surface roughness at least at 400 nm of the outer periphery of the particle of the cathode active material.

[0271] The particle surfaces of the positive electrode active material 100 of this embodiment preferably have a root mean square (RMS) surface roughness, which is an index of roughness, of less than 3 nm, preferably less than 1 nm, and more preferably less than 0.5 nm.

[0272] The image processing software for noise processing, interface extraction, etc. is not particularly limited, but for example, "ImageJ" described in Non-Patent Documents 8 to 10 can be used. The spreadsheet software is also not particularly limited, but for example, Microsoft Office Excel can be used.

[0273] For example, the actual specific surface area S measured by the constant volume gas adsorption method R and the ideal specific surface area S i The smoothness of the surface of the positive electrode active material 100 can also be expressed as a numerical value based on the ratio of the surface smoothness to the surface smoothness.

[0274] Ideal specific surface area S i is calculated assuming that all particles have the same diameter, the same weight, and an ideal spherical shape.

[0275] The median diameter D50 can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a gas adsorption method by a constant volume method, for example.

[0276] The positive electrode active material 100 according to one embodiment of the present invention has an ideal specific surface area S calculated from the median diameter D50. i and the actual specific surface area S R Ratio of S R / S i It is preferable that the ratio is 2.1 or less.

[0277] Alternatively, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 by the following method.

[0278] First, a surface SEM image of the positive electrode active material 100 is obtained. At this time, a conductive coating may be applied as a pretreatment for observation. The observation surface is preferably perpendicular to the electron beam. When comparing multiple samples, the measurement conditions and observation area are the same.

[0279] Next, using image processing software (such as "ImageJ"), the above SEM image is converted to, for example, an 8-bit image (called a grayscale image). A grayscale image contains luminance (brightness information). For example, in an 8-bit grayscale image, luminance can be expressed as 2 to the power of 8 = 256 gradations. Dark areas have lower gradations, and bright areas have higher gradations. The change in luminance can be quantified in relation to the number of gradations. This number is called the grayscale value. Obtaining the grayscale value makes it possible to numerically evaluate the unevenness of the positive electrode active material.

[0280] Furthermore, it is possible to display the brightness change of the target area in a histogram. A histogram is a three-dimensional representation of the gradation distribution in the target area, and is also called a brightness histogram. By obtaining a brightness histogram, it becomes possible to visually understand and evaluate the unevenness of the positive electrode active material.

[0281] In the positive electrode active material 100 according to one embodiment of the present invention, the difference between the maximum and minimum values ​​of the grayscale value is preferably 120 or less, more preferably 115 or less, and even more preferably 70 or more and 115 or less. The standard deviation of the grayscale value is preferably 11 or less, more preferably 8 or less, and even more preferably 4 or more and 8 or less.

[0282] A coating portion may be attached to at least a portion of the surface of the positive electrode active material 100. Fig. 12 shows an example of a positive electrode active material 100 having a coating portion 104 attached thereto.

[0283] The coating portion 104 is preferably formed by the accumulation of decomposition products of the electrolyte and the organic electrolyte solution during charging and discharging. xWhen charging is repeated such that x in CoO2 is 0.24 or less, it is expected that the charge-discharge cycle characteristics will be improved by having a coating portion derived from the electrolyte on the surface of the positive electrode active material 100. This is for reasons such as suppressing an increase in impedance on the surface of the positive electrode active material or suppressing the elution of cobalt. For example, the coating portion 104 preferably contains carbon, oxygen, and fluorine. Furthermore, when LiBOB and / or SUN (suberonitrile) are used as the electrolyte, a good quality coating portion is easily obtained. Therefore, the coating portion 104 having one or more selected from boron, nitrogen, sulfur, and fluorine may be a good quality coating portion and is preferable. In addition, the coating portion 104 does not have to cover the entire positive electrode active material 100. For example, it is sufficient that 50% or more of the surface of the positive electrode active material 100 is covered, more preferably 70% or more, and even more preferably 90% or more.

[0284] This embodiment can be used in combination with other embodiment modes.

[0285] (Embodiment 2) In this embodiment, an example of a method for manufacturing a positive electrode active material 100 which is one embodiment of the present invention will be described with reference to FIGS.

[0286] In order to prepare a positive electrode active material 100 having the distribution, composition, and / or crystal structure of the additive element as described in the previous embodiment, the method of adding the additive element is important. At the same time, it is also important that the crystallinity of the inner portion 100b is good.

[0287] Therefore, in the process of producing the positive electrode active material 100, it is preferable to first synthesize lithium cobalt oxide, and then mix in the additive element source and perform a heat treatment.

[0288] In the method of synthesizing lithium cobalt oxide having an additive element by mixing a cobalt source and a lithium source at the same time, it is difficult to increase the concentration of the additive element in the surface layer portion 100a. Furthermore, if the additive element source is only mixed after the lithium cobalt oxide is synthesized and heating is not performed, the additive element will only adhere to the lithium cobalt oxide without being dissolved in the lithium cobalt oxide. If sufficient heating is not performed, it is difficult to distribute the additive element well. Therefore, it is preferable to mix the additive element source after synthesizing lithium cobalt oxide and perform a heat treatment. This heat treatment after mixing the additive element source is sometimes called annealing.

[0289] However, if the annealing temperature is too high, cation mixing occurs, increasing the possibility that an added element, such as magnesium, will enter the cobalt site. Magnesium present in the cobalt site will be mixed with Li x When x in CoO2 is small, there is no effect of maintaining the layered rock-salt crystal structure of R-3m. Furthermore, if the heat treatment temperature is too high, there are concerns that adverse effects such as cobalt being reduced to divalent and lithium being evaporated may occur.

[0290] Therefore, it is preferable to mix a material that functions as a flux with the additive element source. If the melting point is lower than that of lithium cobalt oxide, the material can function as a flux. For example, fluorine compounds such as lithium fluoride are suitable. Adding a flux lowers the melting point of the additive element source and lithium cobalt oxide. Lowering the melting point makes it easier to distribute the additive element well at a temperature where cation mixing is unlikely to occur.

[0291] [Initial heating] It is more preferable to heat the lithium cobalt oxide after synthesis and before mixing with the additive element. This heating is sometimes called initial heating.

[0292] The initial heating causes lithium to be desorbed from a portion of the surface layer 100a of the lithium cobalt oxide, resulting in a more favorable distribution of the additive elements.

[0293] More specifically, it is believed that initial heating makes it easier to vary the distribution depending on the added element through the following mechanism. First, lithium is removed from part of the surface layer 100a by initial heating. Next, this lithium-deficient surface layer 100a is mixed with an added element source, such as a nickel source, an aluminum source, or a magnesium source, and heated. Of the added elements, magnesium is a typical divalent element, and nickel is a transition metal that is prone to becoming a divalent ion. As a result, Mg is released from part of the surface layer 100a. 2+ and Ni 2+ and Co reduced by lithium deficiency. 2+ However, since this phase is formed only in a part of the surface layer portion 100a, it may not be clearly observed in an electron microscope image such as a STEM or an electron diffraction pattern.

[0294] Among the additive elements, nickel is likely to dissolve in the surface layer 100a of layered rock-salt lithium cobalt oxide and diffuse to the inside 100b, but is likely to remain in the surface layer 100a when part of the surface layer 100a is of the rock-salt type. Therefore, by performing initial heating, it is possible to make it easier for divalent additive elements such as nickel to remain in the surface layer 100a. The effect of this initial heating is particularly large on the surface other than the (001)-oriented surface of the positive electrode active material 100 and on the surface layer 100a.

[0295] In addition, in these rock salt structures, the bond distance between metal Me and oxygen (Me-O distance) tends to be longer than in the layered rock salt structure.

[0296] For example, rock salt Ni 0.5 Mg 0.5 The Me-O distance in the rock salt type MgO is 2.09 Å, and the Me-O distance in the rock salt type MgO is 2.11 Å. Even if a spinel type phase is formed in a part of the surface layer 100a, the Me-O distance in the spinel type NiAl2O4 is 2.0125 Å, and the Me-O distance in the spinel type MgAl2O4 is 2.02 Å. In either case, the Me-O distance exceeds 2 Å. Note that 1 Å=10 -10 m.

[0297] On the other hand, in the layered rock salt type, the bond distance between metals other than lithium and oxygen is shorter than the above. For example, the Al-O distance in layered rock salt type LiAlO2 is 1.905 Å (Li-O distance is 2.11 Å). Also, the Co-O distance in layered rock salt type LiCoO2 is 1.9224 Å (Li-O distance is 2.0916 Å).

[0298] According to Shannon's ionic radii (Non-Patent Document 9), the ionic radius of 6-coordinate aluminum is 0.535 Å, the ionic radius of 6-coordinate oxygen is 1.40 Å, and the sum of these is 1.935 Å.

[0299] From the above, it is considered that aluminum exists more stably in the non-lithium sites of the layered rock-salt type than in the rock-salt type, and therefore aluminum is more likely to be distributed in the deeper region having the layered rock-salt type and / or the interior 100b than in the region close to the surface having the rock-salt type phase in the surface layer portion 100a.

[0300] In addition, the initial heating is expected to have the effect of increasing the crystallinity of the layered rock-salt type crystal structure of the inner portion 100b.

[0301] Therefore, especially Li x When x in CoO2 is, for example, 0.15 or more and 0.17 or less, in order to produce a positive electrode active material 100 having a monoclinic O1(15) type crystal structure, it is preferable to carry out this initial heating.

[0302] However, initial heating is not necessarily required. In other heating steps, such as annealing, the atmosphere, temperature, time, etc. can be controlled to obtain Li x When x in CoO2 is small, it may be possible to produce a positive electrode active material 100 having an O3' type and / or a monoclinic O1(15) type.

[0303] <<Method 1 for preparing positive electrode active material>> Method 1 for producing the positive electrode active material 100 through annealing and initial heating will be described with reference to FIGS. 13(A) to 13(C).

[0304] <Step S11> In step S11 shown in FIG. 13(A), a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials, that is, lithium and transition metal materials, respectively.

[0305] As the lithium source, it is preferable to use a compound containing lithium, such as lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. It is preferable that the lithium source has high purity, and for example, it is preferable to use a material with a purity of 99.99% or more.

[0306] As the cobalt source, it is preferable to use a compound containing cobalt, such as cobalt oxide or cobalt hydroxide.

[0307] The cobalt source is preferably of high purity, for example, a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and even more preferably 5N (99.999%) or more may be used. By using a material of high purity, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is increased and / or the reliability of the secondary battery is improved.

[0308] In addition, it is preferable that the cobalt source has high crystallinity, for example, single crystal grains. The crystallinity of the cobalt source can be evaluated using a TEM (transmission electron microscope) image, a STEM (scanning transmission electron microscope) image, a HAADF-STEM (high-angle annular dark-field scanning transmission electron microscope) image, an ABF-STEM (annular bright-field scanning transmission electron microscope) image, or by X-ray diffraction (XRD), electron diffraction, neutron diffraction, or the like. The above-mentioned methods for evaluating crystallinity can be applied not only to the evaluation of cobalt sources, but also to the evaluation of other crystallinity.

[0309] <Step S12> Next, in step S12 shown in FIG. 13(A), the lithium source and the cobalt source are pulverized and mixed to prepare a mixed material. The pulverization and mixing can be performed in a dry or wet manner. The wet method is preferable because it can be crushed into smaller pieces. When performing the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is more preferable to use an aprotic solvent that does not easily react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. It is preferable to mix the lithium source and the cobalt source with dehydrated acetone with a purity of 99.5% or more, in which the moisture content is suppressed to 10 ppm or less, and then pulverize and mix them. By using dehydrated acetone with the above-mentioned purity, it is possible to reduce impurities that may be mixed in.

[0310] A ball mill, a bead mill, or the like can be used as a means for pulverization and mixing. When using a ball mill, aluminum oxide balls or zirconium oxide balls are preferably used as pulverization media. Zirconium oxide balls are preferred because they emit less impurities. When using a ball mill, a bead mill, or the like, the peripheral speed is preferably set to 100 mm / s or more and 2000 mm / s or less in order to suppress contamination from the media. In this embodiment, the peripheral speed is set to 838 mm / s (rotation speed 400 rpm, ball mill diameter 40 mm).

[0311] <Step S13> Next, in step S13 shown in FIG. 13(A), the mixed material is heated. The heating is preferably performed at 800°C or more and 1100°C or less, more preferably at 900°C or more and 1000°C or less, and even more preferably at about 950°C. If the temperature is too low, the decomposition and melting of the lithium source and the cobalt source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to lithium transpiration from the lithium source and / or cobalt being excessively reduced. For example, cobalt may change from trivalent to divalent, inducing oxygen defects, etc.

[0312] If the heating time is too short, lithium cobalt oxide will not be synthesized, but if it is too long, productivity will decrease. For example, the heating time is preferably 1 hour or more and 100 hours or less, and more preferably 2 hours or more and 20 hours or less.

[0313] The rate of temperature rise depends on the heating temperature reached, but it is recommended to set it to between 80°C / h and 250°C / h. For example, if heating at 1000°C for 10 hours, the rate of temperature rise should be 200°C / h.

[0314] Heating is preferably performed in an atmosphere with little water, such as dry air, for example, with a dew point of -50° C. or less, more preferably with a dew point of -80° C. or less. In this embodiment, heating is performed in an atmosphere with a dew point of -93° C. In order to suppress impurities that may be mixed into the material, it is preferable that the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are each 5 ppb (parts per billion) or less.

[0315] The heating atmosphere is preferably an atmosphere containing oxygen. For example, there is a method of continuously introducing dry air into the reaction chamber. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the reaction chamber and having oxygen flow through the reaction chamber is called flow.

[0316] When the heating atmosphere is an atmosphere containing oxygen, a method that does not allow oxygen to flow may be used. For example, the reaction chamber may be depressurized and then filled with oxygen (or purged) to prevent the oxygen from entering or leaving the reaction chamber. For example, the reaction chamber may be depressurized to -970 hPa and then filled with oxygen to 50 hPa.

[0317] After heating, the material may be naturally cooled, but it is preferable that the time required for the material to cool from the specified temperature to room temperature is within a range of 10 to 50 hours. However, cooling to room temperature is not always necessary, and it is sufficient to cool the material to a temperature that is acceptable for the next step.

[0318] The heating in this step may be performed using a rotary kiln or a roller hearth kiln. Heating using a rotary kiln may be performed while stirring in either a continuous or batch type.

[0319] The crucible used for heating is preferably an aluminum oxide crucible. An aluminum oxide crucible is a material that does not easily release impurities. In this embodiment, an aluminum oxide crucible with a purity of 99.9% is used. It is preferable to place a lid on the crucible when heating it. This can prevent the material from volatilizing.

[0320] In addition, it is preferable to use a used crucible rather than a new one. In this specification, a new crucible refers to one that has undergone the process of putting in and heating materials containing lithium, transition metal M, and / or additive elements two or less times. In addition, a used crucible refers to one that has undergone the process of putting in and heating materials containing lithium, transition metal M, and / or additive elements three or more times. This is because when a new crucible is used, there is a risk that some of the materials, including lithium fluoride, may be absorbed, diffused, moved, and / or attached to the sheath during heating. If some of the materials are lost due to these reasons, there is a growing concern that the distribution of elements in the surface layer of the positive electrode active material will not be within a preferred range. On the other hand, there is less of this risk with a used crucible.

[0321] After the heating is completed, the material may be crushed and sieved as necessary. When recovering the material after heating, it may be transferred from the crucible to a mortar and then recovered. The mortar is preferably made of agate or partially stabilized zirconium oxide. The same heating conditions as those in step S13 can be applied to the heating steps described below other than step S13.

[0322] <Step S14> By the above process, lithium cobalt oxide (LiCoO2) can be synthesized as shown in step S14 of FIG. 13(A).

[0323] Although the example of producing the composite oxide by the solid phase method as in steps S11 to S14 has been shown, the composite oxide may be produced by a coprecipitation method or a hydrothermal method.

[0324] <Step S15> Next, the lithium cobalt oxide is heated in step S15 shown in Fig. 13(A). Since this is the first heating of the lithium cobalt oxide, the heating in step S15 may be called initial heating. Or, since this heating is performed before step S20 described below, it may be called preheating or pretreatment.

[0325] As described above, the initial heating causes lithium to be desorbed from a part of the surface layer 100a of the lithium cobalt oxide. It is also expected to have the effect of increasing the crystallinity of the interior 100b. The lithium source and / or cobalt source prepared in step S11 etc. may contain impurities. The initial heating makes it possible to reduce the impurities in the lithium cobalt oxide completed in step S14.

[0326] Furthermore, the initial heating has the effect of smoothing the surface of the lithium cobalt oxide. For this initial heating, it is not necessary to prepare a lithium source, or an additive element source, or a material that functions as a flux.

[0327] If the heating time of this step is too short, sufficient effect is not obtained, but if it is too long, productivity decreases. For example, the heating conditions can be selected from those described in step S13. In addition to the heating conditions, the heating temperature of this step should be lower than the temperature of step S13 in order to maintain the crystal structure of the complex oxide. Furthermore, the heating time of this step should be shorter than the time of step S13 in order to maintain the crystal structure of the complex oxide. For example, heating should be performed at a temperature of 700°C to 1000°C for 2 hours to 20 hours.

[0328] The effect of increasing the crystallinity of the inner portion 100b is, for example, the effect of mitigating distortion, displacement, and the like resulting from a shrinkage difference or the like possessed by the lithium cobalt oxide produced in step S13.

[0329] The heating in step S13 may cause a temperature difference between the surface and the inside of the lithium cobalt oxide. The temperature difference may induce a shrinkage difference. It is also considered that the temperature difference causes the shrinkage difference because the fluidity of the surface and the inside is different. The energy related to the shrinkage difference gives the lithium cobalt oxide a difference in internal stress. The internal stress difference is also called strain, and the energy is sometimes called strain energy. The internal stress is removed by the initial heating in step S15, or in other words, the strain energy is considered to be homogenized by the initial heating in step S15. When the strain energy is homogenized, the strain of the lithium cobalt oxide is relaxed. As a result, the surface of the lithium cobalt oxide may become smooth. This is also called the surface being improved. In other words, it is considered that the shrinkage difference caused in the lithium cobalt oxide is relaxed after step S15, and the surface of the composite oxide becomes smooth.

[0330] Furthermore, the shrinkage difference may cause microscopic deviations, such as crystal deviations, in the lithium cobalt oxide. In order to reduce such deviations, it is advisable to carry out this step. Through this step, it is possible to equalize the deviations in the composite oxide. When the deviations are equalized, the surface of the composite oxide may become smooth. This is also referred to as the alignment of crystal grains. In other words, it is believed that through step S15, deviations of crystals and the like that have occurred in the composite oxide are alleviated, and the surface of the composite oxide becomes smooth.

[0331] When lithium cobalt oxide, which has a smooth surface, is used as a positive electrode active material, deterioration during charging and discharging as a secondary battery is reduced and cracking of the positive electrode active material can be prevented.

[0332] Note that lithium cobalt oxide synthesized in advance may be used in step S14. In this case, steps S11 to S13 can be omitted. By carrying out step S15 on lithium cobalt oxide synthesized in advance, lithium cobalt oxide with a smooth surface can be obtained.

[0333] <Step S20> Next, as shown in step S20, it is preferable to add the additive element A to the lithium cobalt oxide that has been initially heated. When the additive element A is added to the lithium cobalt oxide that has been initially heated, the additive element A can be added evenly. Therefore, it is preferable to add the additive element A after the initial heating. The step of adding the additive element A will be described with reference to FIG. 13(B) and FIG. 13(C).

[0334] <Step S21> 13B, a source of an additive element A (A source) to be added to lithium cobalt oxide is prepared. A lithium source may be prepared together with the additive element A source.

[0335] The additive element A may be any of the additive elements described in the previous embodiment. Specifically, one or more elements selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, and boron may be used. In addition, one or two elements selected from bromine and beryllium may be used.

[0336] When magnesium is selected as the additive element, the source of the additive element can be called a magnesium source. As the magnesium source, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. can be used. In addition, a plurality of the above-mentioned magnesium sources may be used.

[0337] When fluorine is selected as the additive element, the additive element source can be called a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3), or sodium aluminum hexafluoride (Na3AlF6) can be used. Among these, lithium fluoride is preferred because it has a relatively low melting point of 848° C. and is easily melted in the heating step described below.

[0338] Magnesium fluoride can be used as both the fluorine source and the magnesium source, and lithium fluoride can be used as the lithium source. Another lithium source that can be used in step S21 is lithium carbonate.

[0339] The fluorine source may be a gas, such as fluorine (F2), carbon fluoride, sulfur fluoride, or oxygen fluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F), which may be mixed into the atmosphere in the heating step described below. A plurality of the above-mentioned fluorine sources may be used.

[0340] In this embodiment, lithium fluoride (LiF) is prepared as the fluorine source, and magnesium fluoride (MgF2) is prepared as the fluorine source and magnesium source. When lithium fluoride and magnesium fluoride are mixed at a molar ratio of about LiF:MgF2=65:35, the effect of lowering the melting point is maximized. On the other hand, if the amount of lithium fluoride is large, there is a concern that the lithium becomes excessive and the cycle characteristics deteriorate. Therefore, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≦x≦1.9), more preferably LiF:MgF2=x:1 (0.1≦x≦0.5), and even more preferably LiF:MgF2=x:1 (near x=0.33). In this specification, etc., "near" refers to a value that is greater than 0.9 times and less than 1.1 times the value.

[0341] <Step S22> 13(B), the magnesium source and the fluorine source are pulverized and mixed. This step can be performed under the pulverization and mixing conditions selected from those described in step S12.

[0342] <Step S23> 13(B), the material crushed and mixed as described above is collected to obtain the additive element A source (A source). Note that the additive element A source shown in step S23 has a plurality of starting materials and can be called a mixture.

[0343] The particle size of the mixture is preferably D50 (median diameter) 600 nm to 10 μm, more preferably 1 μm to 5 μm. Even when a single material is used as the additive element source, the D50 (median diameter) is preferably 600 nm to 10 μm, more preferably 1 μm to 5 μm.

[0344] When such a finely powdered mixture (including the case where only one kind of additive element is included) is mixed with lithium cobalt oxide in a later step, the mixture can be easily attached uniformly to the surface of the lithium cobalt oxide particles. If the mixture is attached uniformly to the surface of the lithium cobalt oxide particles, it is preferable because the additive element can be easily distributed or diffused uniformly in the surface layer portion 100a of the composite oxide after heating.

[0345] <Step S21> A process different from that in Fig. 13(B) will be described with reference to Fig. 13(C). In step S21 shown in Fig. 13(C), four types of additive element sources to be added to lithium cobalt oxide are prepared. That is, Fig. 13(C) differs in the types of additive element sources from Fig. 13(B). A lithium source may be prepared together with the additive element sources.

[0346] As sources of four additive elements, a magnesium source (Mg source), a fluorine source (F source), a nickel source (Ni source), and an aluminum source (Al source) are prepared. The magnesium source and the fluorine source can be selected from the compounds described in FIG. 13(B). Nickel oxide, nickel hydroxide, etc. can be used as the nickel source. Aluminum oxide, aluminum hydroxide, etc. can be used as the aluminum source.

[0347] <Steps S22 and S23> Steps S22 and S23 shown in FIG. 13(C) are similar to the steps described in FIG. 13(B).

[0348] <Step S31> 13(A), lithium cobalt oxide is mixed with an additive element A source (A source). The ratio of the number of cobalt atoms Co in the lithium cobalt oxide to the number of magnesium atoms Mg in the additive element A source is preferably Co:Mg=100:y (0.1≦y≦6), and more preferably M:Mg=100:y (0.3≦y≦3).

[0349] The mixing in step S31 is preferably performed under milder conditions than the mixing in step S12 in order not to destroy the shape of the lithium cobalt oxide particles. For example, the mixing is preferably performed under conditions of a lower rotation speed or shorter time than in step S12. It can also be said that the dry method is a milder condition than the wet method. For example, a ball mill, a bead mill, etc. can be used for mixing. When using a ball mill, it is preferable to use zirconium oxide balls as the media.

[0350] In this embodiment, the materials are mixed in a ball mill using zirconium oxide balls with a diameter of 1 mm at 150 rpm for 1 hour in a dry room with a dew point of -100°C or higher and -10°C or lower.

[0351] <Step S32> 13(A), the mixed material is collected to obtain a mixture 903. When collecting the material, it may be crushed and then sieved, if necessary.

[0352] 13A to 13C, a manufacturing method in which an additive element is added only after initial heating is described, but the present invention is not limited to the above method. The additive element may be added at another timing or may be added multiple times. The timing may be changed depending on the element.

[0353] For example, an additive element may be added to the lithium source and the cobalt source in step S11, that is, in the stage of the starting material of the composite oxide. Then, in step S13, lithium cobalt oxide having the additive element can be obtained. In this case, it is not necessary to separate the steps S11 to S14 from the steps S21 to S23. This method can be said to be simple and highly productive.

[0354] Alternatively, lithium cobalt oxide having some of the added elements may be used. For example, if lithium cobalt oxide having magnesium and fluorine added thereto is used, steps S11 to S14 and some of the steps S20 can be omitted. This method is simple and has high productivity.

[0355] Alternatively, lithium cobalt oxide to which magnesium and fluorine have been added in advance may be heated in step S15, and then a magnesium source and a fluorine source, or a magnesium source, a fluorine source, a nickel source and an aluminum source may be added in step S20.

[0356] <Step S33> Next, in step S33 shown in Fig. 13(A), the mixture 903 is heated. The heating conditions can be selected from those described in step S13. The heating time is preferably 2 hours or more. At this time, the pressure inside the furnace may be higher than atmospheric pressure in order to increase the oxygen partial pressure of the heating atmosphere. This is because if the oxygen partial pressure of the heating atmosphere is insufficient, cobalt, etc. will be reduced, and lithium cobalt oxide, etc. may not be able to maintain the layered rock salt type crystal structure.

[0357] Here, a supplementary note on the heating temperature will be provided. The lower limit of the heating temperature in step S33 must be equal to or higher than the temperature at which the reaction between the lithium cobalt oxide and the additive element source proceeds. The temperature at which the reaction proceeds may be any temperature at which interdiffusion of elements contained in the lithium cobalt oxide and the additive element source occurs, and may be lower than the melting temperatures of these materials. An oxide will be used as an example to explain the melting temperature T m 0.757 times (Tammann temperature T d ) solid-phase diffusion occurs. Therefore, the heating temperature in step S33 should be 650° C. or higher.

[0358] Of course, the reaction proceeds more easily if the temperature is equal to or higher than the melting point of one or more of the materials contained in the mixture 903. For example, when LiF and MgF2 are contained as the additive element source, the eutectic point of LiF and MgF2 is around 742°C, so that the lower limit of the heating temperature in step S33 is preferably set to 742°C or higher.

[0359] In addition, the mixture 903 obtained by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) had an initial melting temperature T im is 779℃, melting peak temperature T pm is 815℃, and the melting end temperature T em The lower limit of the heating temperature was 826° C. Therefore, the lower limit of the heating temperature is more preferably 826° C. or higher.

[0360] A higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and the productivity is high.

[0361] The upper limit of the heating temperature is set to be lower than the decomposition temperature (1130°C) of lithium cobalt oxide. At temperatures close to the decomposition temperature, there is a concern that lithium cobalt oxide may decompose, albeit in a small amount. Therefore, the temperature is preferably 1000°C or lower, more preferably 950°C or lower, and even more preferably 900°C or lower.

[0362] Considering these, the heating temperature in step S33 is preferably 650°C to 1130°C, more preferably 650°C to 1000°C, even more preferably 650°C to 950°C, and even more preferably 650°C to 900°C. Also, it is preferably 742°C to 1130°C, more preferably 742°C to 1000°C, even more preferably 742°C to 950°C, and even more preferably 742°C to 900°C. Also, it is preferably 800°C to 1100°C, 830°C to 1130°C, more preferably 830°C to 1000°C, even more preferably 830°C to 950°C, and even more preferably 830°C to 900°C. The heating temperature in step S33 is preferably higher than that in step S13.

[0363] Furthermore, when the mixture 903 is heated, it is preferable to control the partial pressure of fluorine or fluoride resulting from the fluorine source or the like within an appropriate range.

[0364] In the manufacturing method described in this embodiment, some materials, for example, LiF, which is a fluorine source, may function as a flux. This function allows the heating temperature to be lowered to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, to 742°C or higher and 950°C or lower, and additive elements such as magnesium can be distributed in the surface layer to manufacture a positive electrode active material with good characteristics.

[0365] However, since LiF has a lower specific gravity in a gaseous state than oxygen, LiF may volatilize when heated, and if it volatilizes, the amount of LiF in the mixture 903 will decrease. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of LiF. Even if LiF is not used as the fluorine source, etc., Li on the LiCoO2 surface may react with F of the fluorine source to produce LiF, which may then volatilize. Therefore, even if a fluoride with a higher melting point than LiF is used, it is still necessary to suppress the volatilization in the same way.

[0366] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF is high in the heating furnace. By such heating, the volatilization of LiF in the mixture 903 can be suppressed.

[0367] The heating in this step is preferably performed so as not to cause adhesion between particles of the mixture 903. If the particles of the mixture 903 adhere to each other during heating, the contact area with oxygen in the atmosphere decreases, and the route along which the additive element (e.g., fluorine) diffuses is blocked, which may result in poor distribution of the additive element (e.g., magnesium and fluorine) in the surface layer.

[0368] It is also believed that if an additive element (e.g., fluorine) is uniformly distributed in the surface layer, a smooth positive electrode active material with few irregularities can be obtained. Therefore, in order to maintain the smooth surface or to make it even smoother after the heating in step S15 in this process, it is better for the particles of mixture 903 not to stick together.

[0369] In addition, when heating is performed using a rotary kiln, it is preferable to control the flow rate of the oxygen-containing atmosphere in the kiln. For example, it is preferable to reduce the flow rate of the oxygen-containing atmosphere, or to first purge the atmosphere and not flow the atmosphere after introducing the oxygen atmosphere into the kiln. If oxygen is flowed, the fluorine source may evaporate, which is not preferable in terms of maintaining the smoothness of the surface.

[0370] When heating is performed using a roller hearth kiln, the mixture 903 can be heated in an atmosphere containing LiF by, for example, placing a lid on a container containing the mixture 903.

[0371] Regarding the heating time, the heating time varies depending on conditions such as the heating temperature, the size and composition of the lithium cobalt oxide in step S14, etc. When the lithium cobalt oxide is small, a lower temperature or a shorter heating time may be more preferable than when the lithium cobalt oxide is large.

[0372] When the median diameter (D50) of the lithium cobalt oxide in step S14 of Fig. 13(A) is about 12 µm, the heating temperature is preferably, for example, 650°C or more and 950°C or less. The heating time is preferably, for example, 3 hours or more and 60 hours or less, more preferably 10 hours or more and 30 hours or less, and further preferably about 20 hours. The temperature reduction time after heating is preferably, for example, 10 hours or more and 50 hours or less.

[0373] On the other hand, when the median diameter (D50) of the lithium cobalt oxide in step S14 is about 5 μm, the heating temperature is preferably, for example, 650° C. to 950° C. The heating time is preferably, for example, 1 hour to 10 hours, more preferably about 5 hours. The cooling time after heating is preferably, for example, 10 hours to 50 hours.

[0374] <Step S34> Next, in step S34 shown in Fig. 13(A), the heated material is collected and crushed as necessary to obtain the positive electrode active material 100. At this time, it is preferable to further sieve the collected particles. Through the above steps, the positive electrode active material 100 according to one embodiment of the present invention can be produced. The positive electrode active material according to one embodiment of the present invention has a smooth surface.

[0375] <<Method 2 for preparing positive electrode active material>> Next, a method for producing a positive electrode active material, which is one embodiment of the present invention and is different from the method for producing a positive electrode active material, will be described with reference to Fig. 14 to Fig. 15(C). The method for producing a positive electrode active material, which is different from the method for producing a positive electrode active material, is mainly in the number of times that additive elements are added and the mixing method. For other descriptions, the description of the method for producing a positive electrode active material can be referred to.

[0376] In FIG. 14, steps S11 to S15 are carried out in the same manner as in FIG. 13(A) to prepare lithium cobalt oxide that has been subjected to initial heating.

[0377] <Step S20a> Next, as shown in step S20a, it is preferable to add an additive element A1 to the lithium cobalt oxide that has been subjected to the initial heating.

[0378] <Step S21> In step S21 shown in Fig. 15(A), a first additive element source is prepared. The first additive element source can be selected from the additive elements A described in step S21 shown in Fig. 13(B) and used. For example, the additive element A1 can be one or more selected from magnesium, fluorine, and calcium. Fig. 15(A) illustrates an example in which a magnesium source (Mg source) and a fluorine source (F source) are used as the first additive element source.

[0379] Steps S21 to S23 shown in Fig. 15(A) can be performed under the same conditions as steps S21 to S23 shown in Fig. 13(B). As a result, an additive element source (A1 source) can be obtained in step S23.

[0380] Moreover, steps S31 to S33 shown in FIG. 14 can be performed in the same manner as steps S31 to S33 shown in FIG. 13(A).

[0381] <Step S34a> Next, in step S33, the heated material is collected to produce lithium cobalt oxide containing the additive element A1. This is also called a second composite oxide to distinguish it from the composite oxide in step S14.

[0382] <Step S40> In step S40 shown in Fig. 14, the additive element A2 is added. Description will be made with reference to Figs. 15(B) and 15(C).

[0383] <Step S41> In step S41 shown in Fig. 15(B), a second additive element source is prepared. The second additive element source can be selected from the additive elements A described in step S21 shown in Fig. 13(B) and used. For example, the additive element A2 can be one or more selected from nickel, titanium, boron, zirconium, and aluminum. Fig. 15(B) illustrates an example in which a nickel source (Ni source) and an aluminum source (Al source) are used as the second additive element source.

[0384] Steps S41 to S43 shown in Fig. 15(B) can be performed under the same conditions as steps S21 to S23 shown in Fig. 13(B) As a result, an additive element source (A2 source) can be obtained in step S43.

[0385] Moreover, Fig. 15(C) shows a modified example of the steps described with reference to Fig. 15(B). In step S41 shown in Fig. 15(C), a nickel source (Ni source) and an aluminum source (Al source) are prepared, and in step S42a, they are each independently pulverized. As a result, in step S43, a plurality of second additive element sources (A2 sources) are prepared. The steps in Fig. 15(C) differ from Fig. 15(B) in that the additive elements are independently pulverized in step S42a.

[0386] <Steps S51 to S53> Next, steps S51 to S53 shown in Fig. 14 can be performed under the same conditions as steps S31 to S34 shown in Fig. 13(A). The conditions for step S53 relating to the heating step may be a lower temperature and a shorter time than those for step S33. Through the above steps, in step S54, a positive electrode active material 100 according to one embodiment of the present invention can be produced. The positive electrode active material according to one embodiment of the present invention has a smooth surface.

[0387] 14 to 15(C), in the manufacturing method 2, the additive element A1 and the additive element A2 are introduced separately into the lithium cobalt oxide. By introducing the additive elements separately, the concentration distribution of each additive element in the depth direction can be changed. For example, it is possible to distribute the additive element A1 so that the concentration is higher in the surface layer portion 100a than in the inside 100b, and distribute the additive element A2 so that the concentration is higher in the inside 100b than in the surface layer portion 100a.

[0388] By undergoing the initial heating described in this embodiment, a positive electrode active material with a smooth surface can be obtained.

[0389] The initial heating shown in this embodiment is performed on lithium cobalt oxide. Therefore, the initial heating is preferably performed under conditions of a heating temperature lower than that for obtaining lithium cobalt oxide and a heating time shorter than that for obtaining lithium cobalt oxide. The step of adding an additive element to lithium cobalt oxide is preferably performed after the initial heating. The addition step can be divided into two or more steps. By following such a step order, the smoothness of the surface obtained by the initial heating is preferably maintained.

[0390] Positive electrode active material 100 with a smooth surface may be more resistant to physical destruction due to pressure, etc. than positive electrode active materials that do not have a smooth surface. For example, positive electrode active material 100 is less likely to be destroyed in a test involving pressure, such as a nail penetration test, and as a result, safety may be improved.

[0391] This embodiment mode can be used in combination with other embodiment modes.

[0392] (Embodiment 3) In this embodiment, an example of a secondary battery of one embodiment of the present invention will be described with reference to FIGS.

[0393] <Example of secondary battery configuration> The following description will be given taking as an example a secondary battery shown in FIG. 16 in which a positive electrode, a negative electrode, and an electrolyte are enclosed in an exterior body.

[0394] [Positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and may include a conductive material (synonymous with a conductive additive) and a binder. The positive electrode active material is prepared by the method described in the above embodiment.

[0395] The positive electrode active material described in the above embodiment may be mixed with another positive electrode active material.

[0396] Examples of other cathode active materials include composite oxides having an olivine-type crystal structure, a layered rock salt-type crystal structure, or a spinel-type crystal structure. Examples of such compounds include LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2.

[0397] In addition, as another cathode active material, a lithium-containing material having a spinel-type crystal structure containing manganese such as LiMn2O4 is preferably mixed with lithium nickelate (LiNiO2 or LiNi 1-x M x O2 (0 < x < 1) (M = Co, Al, etc.). By adopting such a configuration, the characteristics of the secondary battery can be improved.

[0398] As the conductive material, carbon-based materials such as acetylene black can be used. In addition, carbon nanotubes, graphene, or graphene compounds can be used as the conductive material.

[0399] In this specification and the like, the graphene compound includes multi-layer graphene, multi-graphene, graphene oxide, multi-layer graphene oxide, multi-oxide graphene, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-oxide graphene, graphene quantum dots, and the like. The graphene compound refers to a material having carbon, having a flat or sheet-like shape, and having a two-dimensional structure formed by carbon six-membered rings. The two-dimensional structure formed by the carbon six-membered rings is sometimes referred to as a carbon sheet. The graphene compound may have a functional group. In addition, the graphene compound preferably has a bent shape. Also, the graphene compound may be rounded to be like a carbon nanofiber.

[0400] In this specification and the like, graphene oxide refers to a material having carbon and oxygen, having a sheet-like shape, and having a functional group, particularly an epoxy group, a carboxyl group, or a hydroxy group.

[0401] In the present specification and the like, reduced graphene oxide refers to a graphene oxide having a sheet-like shape and a two-dimensional structure formed of six-membered carbon rings, which contains carbon and oxygen. Although reduced graphene oxide functions as a single sheet, multiple sheets may be stacked. Reduced graphene oxide preferably has a portion in which the carbon concentration is greater than 80 atomic % and the oxygen concentration is 2 atomic % to 15 atomic %. By setting such carbon and oxygen concentrations, it can function as a conductive material with high conductivity even in a small amount. In addition, reduced graphene oxide preferably has an intensity ratio G / D of G band to D band in Raman spectrum of 1 or more. Reduced graphene oxide with such an intensity ratio can function as a conductive material with high conductivity even in a small amount.

[0402] The graphene compound may have excellent electrical properties such as high electrical conductivity, and excellent physical properties such as high flexibility and high mechanical strength. The graphene compound may have a sheet-like shape. The graphene compound may have a curved surface, enabling surface contact with low contact resistance. In addition, even if the graphene compound is thin, it may have very high electrical conductivity, and a small amount of the graphene compound may efficiently form a conductive path in the active material layer. Therefore, by using the graphene compound as a conductive material, the contact area between the active material and the conductive material can be increased. The graphene compound may cover 80% or more of the area of ​​the active material. It is preferable that the graphene compound is wrapped around at least a part of the active material particles. It is also preferable that the graphene compound is overlapped on at least a part of the active material particles. It is also preferable that the shape of the graphene compound matches at least a part of the shape of the active material particles. The shape of the active material particles refers to, for example, the unevenness of a single active material particle or the unevenness formed by a plurality of active material particles. It is also preferable that the graphene compound surrounds at least a part of the active material particles. The graphene compound may have holes.

[0403] When using active material particles having a small particle size, for example, active material particles having a size of 1 μm or less, the specific surface area of ​​the active material particles is large, and more conductive paths connecting the active material particles are required. In such a case, it is preferable to use a graphene compound that can efficiently form conductive paths even in a small amount.

[0404] Because of the above-mentioned properties, it is particularly effective to use a graphene compound as a conductive material for secondary batteries that require rapid charging and rapid discharging. For example, secondary batteries for two-wheeled or four-wheeled vehicles and secondary batteries for drones may require rapid charging and rapid discharging characteristics. In addition, rapid charging characteristics may be required for mobile electronic devices. Rapid charging and discharging refers to charging and discharging at, for example, 200 mA / g, 400 mA / g, or 1000 mA / g or more.

[0405] The multiple graphenes or graphene compounds are formed so as to partially cover the multiple granular positive electrode active material particles or to be attached to surfaces of the multiple granular positive electrode active material particles, and therefore are preferably in surface contact with each other.

[0406] Here, a mesh-like graphene compound sheet (hereinafter referred to as a graphene compound net or graphene net) can be formed by bonding multiple graphenes or graphene compounds together. When an active material is covered with a graphene net, the graphene net can also function as a binder that bonds the active materials together. Therefore, the amount of binder can be reduced or no binder can be used, and the ratio of the active material to the electrode volume and electrode weight can be improved. That is, the discharge capacity of the secondary battery can be increased.

[0407] In addition, a material used in forming the graphene compound may be mixed with the graphene compound and used in the active material layer. For example, particles used as a catalyst in forming the graphene compound may be mixed with the graphene compound. Examples of catalysts used in forming the graphene compound include silicon oxide (SiO2, SiO x(x<2)), aluminum oxide, iron, nickel, ruthenium, iridium, platinum, copper, germanium, etc. The particles preferably have a median diameter (D50) of 1 μm or less, more preferably 100 nm or less.

[0408] [Binder] As the binder, it is preferable to use a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. Also, as the binder, fluororubber can be used.

[0409] In addition, it is preferable to use, for example, a water-soluble polymer as the binder. For example, polysaccharides can be used as the water-soluble polymer. For the polysaccharides, one or more of cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, and starch can be used. It is even more preferable to use these water-soluble polymers in combination with the above-mentioned rubber material.

[0410] Alternatively, it is preferable to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (polymethyl methacrylate, PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose as the binder.

[0411] The binder may be used in combination of two or more of the above.

[0412] [Current collector] As the current collector, a material having high electrical conductivity, such as metals such as stainless steel, gold, platinum, aluminum, and titanium, and alloys thereof, can be used. In addition, it is preferable that the material used for the positive electrode current collector does not dissolve at the potential of the positive electrode. In addition, an aluminum alloy to which an element that improves heat resistance, such as silicon, titanium, neodymium, scandium, or molybdenum, is added can be used. In addition, it may be formed of a metal element that reacts with silicon to form a silicide. Examples of the metal element that reacts with silicon to form a silicide include zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, and nickel. The current collector can be appropriately used in the form of a foil, plate, sheet, net, punched metal, or expanded metal. It is preferable to use a current collector having a thickness of 5 μm or more and 30 μm or less.

[0413] [Negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may include a conductive material and a binder.

[0414] [Negative electrode active material] As the negative electrode active material, for example, an alloy-based material and / or a carbon-based material can be used.

[0415] As the negative electrode active material, an element capable of carrying out a charge / discharge reaction by alloying / dealloying reaction with lithium can be used. For example, a material containing one or more elements selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc. can be used. Such elements have a larger charge / discharge capacity than carbon, and silicon in particular has a high theoretical capacity of 4200mAh / g. For this reason, it is preferable to use silicon as the negative electrode active material. Compounds containing these elements may also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb, SbSn, etc. Here, elements capable of undergoing charge / discharge reactions through alloying / dealloying reactions with lithium, and compounds containing such elements, are sometimes referred to as alloying materials.

[0416] In this specification, SiO refers to, for example, silicon monoxide. Alternatively, SiO x Here, x preferably has a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, more preferably 0.3 or more and 1.2 or less, or preferably 0.2 or more and 1.2 or less, or preferably 0.3 or more and 1.5 or less.

[0417] Examples of the carbon-based material that can be used include graphite, easily graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), carbon nanotubes, graphene, and carbon black.

[0418] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, MCMB may have a spherical shape, which is preferable. In addition, it is relatively easy to reduce the surface area of ​​MCMB, which may be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.

[0419] When lithium ions are inserted into graphite (when lithium-graphite intercalation compounds are formed), graphite exhibits a low potential similar to that of lithium metal (0.05 V to 0.3 V vs. Li / Li + ) This allows lithium-ion secondary batteries to exhibit high operating voltages. Furthermore, graphite is preferred because it has the advantages of relatively high charge / discharge capacity per unit volume, relatively small volume expansion, low cost, and high safety compared to lithium metal.

[0420] In addition, titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten oxide (WO2), molybdenum oxide (MoO2), and other oxides can be used.

[0421] In addition, the negative electrode active material is Li3N-type Li, a complex nitride of lithium and transition metals. 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N3 has a large charge / discharge capacity (900mAh / g, 1890mAh / cm 3 ) and is preferred.

[0422] When a composite nitride of lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, and therefore it is preferable to combine it with a material that does not contain lithium ions, such as V2O5 or Cr3O8, as the positive electrode active material. Even when a material that contains lithium ions is used as the positive electrode active material, the composite nitride of lithium and a transition metal can be used as the negative electrode active material by first removing the lithium ions contained in the positive electrode active material.

[0423] In addition, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example, transition metal oxides that do not form an alloy with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as the negative electrode active material. Further examples of materials that undergo a conversion reaction include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, and CoS 0.89 It also occurs in sulfides such as NiS and CuS, nitrides such as Zn3N2, Cu3N and Ge3N4, phosphides such as NiP2, FeP2 and CoP3, and fluorides such as FeF3 and BiF3.

[0424] As the conductive material and binder that can be contained in the negative electrode active material layer, materials similar to the conductive material and binder that can be contained in the positive electrode active material layer can be used.

[0425] [Negative electrode current collector] The negative electrode current collector may be made of the same material as the positive electrode current collector, but it is preferable that the negative electrode current collector is made of a material that does not form an alloy with carrier ions such as lithium.

[0426] [Electrolyte] The electrolytic solution has a solvent and an electrolyte. The solvent of the electrolytic solution is preferably an aprotic organic solvent, and for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio.

[0427] In addition, by using one or more ionic liquids (room-temperature molten salts) that are flame-retardant and non-volatile as a solvent for the electrolyte, even if the internal temperature of the secondary battery rises due to an internal short circuit or overcharging, etc., the secondary battery can be prevented from bursting and / or catching fire. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolyte include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, and aromatic cations such as imidazolium cations and pyridinium cations. Examples of the anion used in the electrolyte include monovalent amide anions, monovalent methide anions, fluorosulfonic acid anions, perfluoroalkylsulfonic acid anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, and perfluoroalkylphosphate anions.

[0428] Examples of the electrolyte to be dissolved in the above-mentioned solvent include LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, and Li2B 10 Cl 10 , Li2B12 Cl 12 Lithium salts such as LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, etc. can be used alone or in any combination and ratio of two or more of these.

[0429] The electrolyte used in the secondary battery is preferably a highly purified electrolyte with a low content of granular waste or elements other than the constituent elements of the electrolyte (hereinafter, simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolyte is preferably 1% or less, more preferably 0.1% or less, and even more preferably 0.01% or less.

[0430] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate)borate (LiBOB), dinitrile compounds such as succinonitrile and adiponitrile, fluorobenzene, and ethyleneglycolbis(propionitrile)ether may be added to the electrolyte. The concentration of each of the added materials may be, for example, 0.1 wt% to 5 wt% relative to the entire solvent. VC and LiBOB are particularly preferred because they are easy to form a good coating portion.

[0431] Alternatively, a polymer gel electrolyte may be used in which a polymer is swollen with an electrolytic solution.

[0432] The use of a polymer gel electrolyte improves safety against leakage, etc. Also, it is possible to make the secondary battery thinner and lighter.

[0433] Examples of the polymer that can be gelled include silicone gel, acrylic gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, and fluorine-based polymer gel.

[0434] Examples of the polymer that can be used include polymers having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, polyacrylonitrile, and copolymers containing these. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. The polymer that is formed may have a porous shape.

[0435] In addition, instead of the electrolyte, a solid electrolyte containing an inorganic material such as a sulfide or oxide, or a solid electrolyte containing a polymer material such as a PEO (polyethylene oxide) can be used. When a solid electrolyte is used, the installation of a separator and / or spacer becomes unnecessary. In addition, since the entire battery can be solidified, there is no risk of leakage, and safety is dramatically improved.

[0436] [Separator] The secondary battery preferably has a separator. The separator may be made of, for example, paper, nonwoven fabric, glass fiber, ceramics, or synthetic fibers such as nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic, polyolefin, or polyurethane. The separator is preferably processed into an envelope shape and disposed so as to encase either the positive electrode or the negative electrode.

[0437] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene or polyethylene may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. As the ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As the fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As the polyamide material, for example, nylon or aramid (meta-aramid or para-aramid) may be used.

[0438] Coating with ceramic materials improves oxidation resistance, suppressing the deterioration of the separator during high-voltage charging and discharging, and improving the reliability of the secondary battery. Coating with fluorine-based materials also improves adhesion between the separator and electrodes, improving output characteristics. Coating with polyamide-based materials, especially aramid, improves heat resistance, improving the safety of the secondary battery.

[0439] For example, both sides of a polypropylene film may be coated with a mixture of aluminum oxide and aramid.Alternatively, the surface of the polypropylene film that contacts the positive electrode may be coated with a mixture of aluminum oxide and aramid, and the surface that contacts the negative electrode may be coated with a fluorine-based material.

[0440] By using a separator with a multi-layer structure, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin, and therefore the discharge capacity per volume of the secondary battery can be increased.

[0441] [Exterior body] The exterior body of the secondary battery can be made of, for example, a metal material such as aluminum and / or a resin material. Also, a film-shaped exterior body can be used. As the film, for example, a three-layer structure film can be used in which a thin metal film having excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide-based resin, polyester-based resin, etc. is further provided on the thin metal film as the outer surface of the exterior body.

[0442] <Laminated secondary battery and its manufacturing method> An example of an external view of a laminated secondary battery 500 is shown in Fig. 16 and Fig. 17. Fig. 16 and Fig. 17 show a positive electrode 503 having a positive electrode current collector 501 and a positive electrode active material layer 502, a negative electrode 506 having a negative electrode current collector 504 and a negative electrode active material layer 505, a separator 507, an exterior body 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511. If the laminated secondary battery has a flexible structure, the secondary battery can be bent according to the deformation of the electronic device when mounted in an electronic device having at least a part having flexibility. An example of a method for manufacturing the laminated secondary battery will be described with reference to Figs. 17(A) to 17(C).

[0443] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. FIG. 17(B) shows the laminated negative electrode 506, the separator 507, and the positive electrode 503. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. Next, the tab regions of the positive electrodes 503 are bonded to each other, and the positive electrode lead electrode 510 is bonded to the tab region of the outermost positive electrode. For example, ultrasonic welding or the like may be used for the bonding. Similarly, the tab regions of the negative electrodes 506 are bonded to each other, and the negative electrode lead electrode 511 is bonded to the tab region of the outermost negative electrode.

[0444] Next, the negative electrode 506 , the separator 507 and the positive electrode 503 are placed on the exterior body 509 .

[0445] Next, as shown in Fig. 17(C), exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of exterior body 509 so that an electrolyte can be introduced later.

[0446] Next, an electrolyte (not shown) is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The introduction of the electrolyte is preferably performed under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, the laminate type secondary battery 500 can be produced.

[0447] By using the positive electrode active material described in the above embodiment for the positive electrode 503, the secondary battery 500 can have a high discharge capacity and excellent cycle characteristics.

[0448] This embodiment mode can be used in appropriate combination with other embodiment modes.

[0449] (Embodiment 4) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted on an electronic device will be described with reference to FIGS.

[0450] 18A to 18G show examples of electronic devices to which the secondary battery having the positive electrode active material described in the above embodiment is mounted. Examples of electronic devices to which the secondary battery is applied include television devices (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, personal digital assistants, audio playback devices, and large game machines such as pachinko machines.

[0451] Furthermore, a secondary battery having a flexible shape can be incorporated along the curved surfaces of the inner or outer walls of a house or building, or the interior or exterior of an automobile.

[0452] 18A shows an example of a mobile phone. The mobile phone 7400 includes a display portion 7402 built into a housing 7401, operation buttons 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like. Note that the mobile phone 7400 includes a secondary battery 7407. By using the secondary battery of one embodiment of the present invention as the secondary battery 7407, a lightweight mobile phone with a long life can be provided.

[0453] FIG. 18(B) shows a state in which the mobile phone 7400 is bent. When the mobile phone 7400 is deformed by an external force to bend the entire mobile phone 7400, the secondary battery 7407 provided therein is also bent. FIG. 18(C) shows the state of the bent secondary battery 7407 at that time. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to a current collector. For example, the current collector is a copper foil, and a part of the current collector is alloyed with gallium to improve adhesion with the active material layer in contact with the current collector, so that the secondary battery 7407 has a high reliability when bent.

[0454] FIG. 18D shows an example of a bangle-type display device. The portable display device 7100 includes a housing 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 18E shows a bent state of the secondary battery 7104. When the secondary battery 7104 is worn on a user's arm in a bent state, the housing is deformed, and the curvature of the secondary battery 7104 changes in part or in whole. Note that the degree of bending at any point of the curve expressed by the value of the radius of the corresponding circle is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, the housing or the main surface of the secondary battery 7104 changes in part or in whole when the radius of curvature is in the range of 40 mm to 150 mm. High reliability can be maintained if the radius of curvature of the main surface of the secondary battery 7104 is in the range of 40 mm to 150 mm. By using the secondary battery of one embodiment of the present invention as the secondary battery 7104, a lightweight portable display device with a long life can be provided.

[0455] 18F shows an example of a wristwatch-type portable information terminal. A portable information terminal 7200 includes a housing 7201, a display portion 7202, a band 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.

[0456] The portable information terminal 7200 can execute various applications such as mobile telephone, e-mail, document browsing and creation, music playback, Internet communication, and computer games.

[0457] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. The display portion 7202 is also provided with a touch sensor, and can be operated by touching the screen with a finger, a stylus, or the like. For example, an application can be started by touching an icon 7207 displayed on the display portion 7202.

[0458] The operation button 7205 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 7205 can be freely set by an operating system built into the mobile information terminal 7200.

[0459] The mobile information terminal 7200 can also perform short-distance wireless communication according to a communication standard. For example, the mobile information terminal 7200 can communicate with a wireless headset to enable hands-free calling.

[0460] The portable information terminal 7200 also includes an input / output terminal 7206, and can directly exchange data with another information terminal via a connector. Charging can also be performed via the input / output terminal 7206. Note that charging may be performed by wireless power supply without using the input / output terminal 7206.

[0461] A display portion 7202 of a portable information terminal 7200 includes the secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a portable information terminal that is lightweight and has a long life can be provided. For example, the secondary battery 7104 shown in FIG. 18E can be incorporated in a curved state inside a housing 7201 or in a bendable state inside a band 7203.

[0462] The portable information terminal 7200 preferably has a sensor. For example, it is preferable that a fingerprint sensor, a pulse sensor, a human body sensor such as a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like is mounted as the sensor.

[0463] 18G illustrates an example of an armband-type display device. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 can also include a touch sensor in the display portion 7304 and can function as a portable information terminal.

[0464] The display surface of the display portion 7304 is curved, and display can be performed along the curved display surface. In addition, the display device 7300 can change the display state by short-range wireless communication according to a communication standard.

[0465] The display device 7300 also includes an input / output terminal, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal. Note that charging may be performed by wireless power supply without using the input / output terminal.

[0466] By using the secondary battery of one embodiment of the present invention as a secondary battery included in the display device 7300, a lightweight display device with a long lifetime can be provided.

[0467] In addition, an example in which the secondary battery having good cycle characteristics described in the above embodiment is mounted on an electronic device will be described with reference to FIGS.

[0468] By using the secondary battery of one embodiment of the present invention as a secondary battery in daily electronic devices, products that are lightweight and have a long life can be provided. For example, daily electronic devices include electric toothbrushes, electric shavers, and electric beauty devices. For the secondary battery of these products, a stick-shaped secondary battery that is small, lightweight, and has a large discharge capacity is desired in consideration of ease of holding by users.

[0469] FIG. 18(H) is a perspective view of a device also called a tobacco-receiving smoking device (electronic cigarette). In FIG. 18(H), the electronic cigarette 7500 is composed of an atomizer 7501 including a heating element, a secondary battery 7504 that supplies power to the atomizer, and a cartridge 7502 including a liquid supply bottle, a sensor, and the like. To enhance safety, a protection circuit that prevents overcharging and / or overdischarging of the secondary battery 7504 may be electrically connected to the secondary battery 7504. The secondary battery 7504 shown in FIG. 18(H) has an external terminal so that it can be connected to a charging device. Since the secondary battery 7504 is the tip part when held, it is desirable that the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high discharge capacity and good cycle characteristics, a small and lightweight electronic cigarette 7500 that can be used for a long period of time can be provided.

[0470] Fig. 19(A) shows an example of a wearable device. The wearable device uses a secondary battery as a power source. In addition, when a user uses the device in daily life or outdoors, in order to improve splash-proof performance, water resistance, or dust resistance, there is a demand for a wearable device that can be charged wirelessly as well as by wire with an exposed connector.

[0471] For example, the secondary battery according to one embodiment of the present invention can be mounted on a glasses-type device 4000 as shown in FIG. 19A. The glasses-type device 4000 includes a frame 4000a and a display unit 4000b. By mounting a secondary battery on the temples of the curved frame 4000a, the glasses-type device 4000 can be lightweight, well-balanced in weight, and has a long continuous use time. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a smaller housing can be realized.

[0472] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the headset type device 4001. The headset type device 4001 has at least a microphone unit 4001a, a flexible pipe 4001b, and an earphone unit 4001c. The secondary battery can be provided in the flexible pipe 4001b and / or the earphone unit 4001c. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a miniaturized housing can be realized.

[0473] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. A secondary battery 4002b can be provided in a thin housing 4002a of the device 4002. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0474] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided in a thin housing 4003a of the device 4003. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0475] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the belt type device 4006. The belt type device 4006 has a belt portion 4006a and a wireless power receiving portion 4006b, and a secondary battery can be mounted inside the belt portion 4006a. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.

[0476] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the wristwatch device 4005. The wristwatch device 4005 has a display portion 4005a and a belt portion 4005b, and the secondary battery can be provided on the display portion 4005a or the belt portion 4005b. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.

[0477] The display unit 4005a can display not only the time, but also various other information such as incoming e-mails and phone calls.

[0478] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the arm, it may be equipped with sensors that measure the user's pulse, blood pressure, etc. Data on the user's amount of exercise and health can be accumulated to manage the user's health.

[0479] FIG. 19(B) shows a perspective view of the wristwatch type device 4005 removed from the wrist.

[0480] 19C is a side view. Fig. 19C shows a state in which a secondary battery 913 is built in. The secondary battery 913 is the secondary battery described in Embodiment 4. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.

[0481] 19(D) shows an example of a wireless earphone. Here, the wireless earphone is illustrated having a pair of main bodies 4100a and 4100b, but the pair is not necessarily required.

[0482] The main bodies 4100a and 4100b each have a driver unit 4101, an antenna 4102, and a secondary battery 4103. They may also have a display unit 4104. They also preferably have a substrate on which a circuit such as a wireless IC is mounted, a charging terminal, and the like. They may also have a microphone.

[0483] The case 4110 has a secondary battery 4111. It is preferable that the case 4110 also has a board on which circuits such as a wireless IC and a charge control IC are mounted, and a charging terminal. It may also have a display unit, buttons, and the like.

[0484] The main units 4100a and 4100b can wirelessly communicate with other electronic devices such as smartphones. This allows the main units 4100a and 4100b to play back audio data sent from other electronic devices. If the main units 4100a and 4100b have a microphone, the audio captured by the microphone can be sent to the other electronic device, and the audio data processed by the electronic device can be sent back to the main units 4100a and 4100b for playback. This allows the main units 4100a and 4100b to be used as a translator, for example.

[0485] In addition, the secondary battery 4103 in the main body 4100a can be charged from the secondary battery 4111 in the case 4110. The coin-type secondary battery, the cylindrical secondary battery, or the like described in the previous embodiments can be used as the secondary battery 4111 and the secondary battery 4103. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 as a positive electrode has a high energy density, and by using the secondary battery 4103 and the secondary battery 4111, a configuration that can accommodate space saving associated with miniaturization of wireless earphones can be realized.

[0486] 20A shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port arranged on the bottom surface.

[0487] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may become entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component therein. By using the secondary battery 6306 according to one embodiment of the present invention in the cleaning robot 6300, the cleaning robot 6300 can be an electronic device with long operating time and high reliability.

[0488] Fig. 20B shows an example of a robot. The robot 6400 shown in Fig. 20B includes a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0489] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.

[0490] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may also be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.

[0491] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.

[0492] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component inside the robot 6400. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be a highly reliable electronic device with a long operating time.

[0493] Fig. 20C shows an example of an aircraft. An aircraft 6500 shown in Fig. 20C includes a propeller 6501, a camera 6502, a secondary battery 6503, and the like, and has a function of flying autonomously.

[0494] For example, image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can analyze the image data and detect the presence or absence of an obstacle when moving. The electronic component 6504 can estimate the remaining battery charge from a change in the power storage capacity of the secondary battery 6503. The flying object 6500 includes therein the secondary battery 6503 according to one embodiment of the present invention. By using the secondary battery according to one embodiment of the present invention in the flying object 6500, the flying object 6500 can be an electronic device with a long operating time and high reliability.

[0495] This embodiment mode can be implemented in appropriate combination with other embodiment modes.

[0496] (Embodiment 5) In this embodiment, an example is described in which a secondary battery including the positive electrode active material of one embodiment of the present invention is mounted on a vehicle.

[0497] By installing secondary batteries in vehicles, next-generation clean energy vehicles such as hybrid vehicles (HVs), electric vehicles (EVs), and plug-in hybrid vehicles (PHVs) can be realized.

[0498] FIG. 21 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. An automobile 8400 illustrated in FIG. 21A is an electric automobile using an electric motor as a power source for running. Alternatively, it is a hybrid automobile in which an electric motor and an engine can be appropriately selected and used as a power source for running. By using one embodiment of the present invention, a vehicle with a long cruising distance can be realized. In addition, the automobile 8400 has a secondary battery. For example, secondary battery modules can be arranged on the floor of the vehicle. The secondary battery can not only drive the electric motor 8406 but also supply power to light-emitting devices such as a headlight 8401 and a room light (not shown).

[0499] The secondary battery can also supply power to display devices such as a speedometer and a tachometer included in the automobile 8400. The secondary battery can also supply power to semiconductor devices such as a navigation system included in the automobile 8400.

[0500] The automobile 8500 shown in FIG. 21(B) can charge the secondary battery of the automobile 8500 by receiving power supply from an external charging facility by a plug-in method and / or a non-contact power supply method. FIG. 21(B) shows a state in which a secondary battery 8024 mounted on the automobile 8500 is being charged from a ground-mounted charging device 8021 via a cable 8022. When charging, the charging method and connector standards may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or combo. The charging device 8021 may be a charging station installed in a commercial facility or a home power source. For example, the secondary battery 8024 mounted on the automobile 8500 can be charged by an external power supply using plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.

[0501] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in the road and / or an exterior wall, charging may be performed not only while the vehicle is stopped but also while it is moving. This contactless power supply method may also be used to transmit and receive power between vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped and / or moving. For such contactless power supply, an electromagnetic induction method and / or a magnetic field resonance method may be used.

[0502] 21C is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. A scooter 8600 shown in FIG. 21C includes a secondary battery 8602, a side mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply electricity to the turn signal light 8603.

[0503] 21(C) is capable of storing a secondary battery 8602 in the under-seat storage 8604. Even if the under-seat storage 8604 is small, the secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 is removable, and when charging, the secondary battery 8602 can be carried indoors, charged, and stored before riding.

[0504] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the discharge capacity of the secondary battery can be increased. Therefore, the secondary battery itself can be made small and lightweight. If the secondary battery itself can be made small and lightweight, it contributes to reducing the weight of the vehicle, and the cruising distance can be improved. In addition, the secondary battery mounted on the vehicle can be used as a power supply source other than the vehicle. In this case, for example, it is possible to avoid using a commercial power source during peak power demand. If it is possible to avoid using a commercial power source during peak power demand, it is possible to contribute to energy conservation and reduction of carbon dioxide emissions. In addition, if the cycle characteristics are good, the secondary battery can be used for a long period of time, and the amount of rare metals used, including cobalt, can be reduced.

[0505] This embodiment mode can be implemented in appropriate combination with other embodiment modes. [Explanation of symbols]

[0506] 100 Cathode active material 100a Surface layer 100b internal 104 Covering part 110 Cluster

Claims

1. A secondary battery having a positive electrode, The positive electrode has a positive electrode active material, The positive electrode active material contains lithium, cobalt, oxygen, and magnesium, and has a layered rock salt type crystal structure, The positive electrode active material is The positive electrode active material has magnesium oxide clusters therein, The clusters have a rock-salt type crystal structure.

2. A secondary battery having a positive electrode, The positive electrode has a positive electrode active material, The positive electrode active material contains lithium, cobalt, oxygen, magnesium, and nickel, and has a layered rock salt type crystal structure; The positive electrode active material is The positive electrode active material has magnesium oxide clusters therein, The cluster has a rock-salt crystal structure, The clusters have nickel surrounding them.

3. In claim 2, A secondary battery, wherein the ratio of Mg / Ni (atomic number ratio) within the positive electrode active material is 0.8 or more and 1.2 or less.

4. In any one of claims 1 to 3, The magnesium oxide clusters have a function of relieving stress of the positive electrode active material.

5. In any one of claims 1 to 3, The magnesium oxide clusters have a smaller volume change upon charging and discharging than the layered rock salt type crystal structure.

6. An electronic device comprising the secondary battery according to claim 5.

7. A vehicle comprising the secondary battery according to claim 5.

Citation Information

Patent Citations

  • Positive electrode active material, method for manufacturing positive electrode active material, and secondary battery

    JP2018206747A

  • Secondary battery and electronic apparatus

    JP2022070247A